Endolithic fungal diversity is present in the unique phosphatized rocks of an environmentally extreme equatorial archipelago revealed by DNA amplicon metagenomics - Laucélly Bárbara Avelar Rocha; Vívian Nicolau Gonçalves; Fábio Soares de Oliveira; Guilherme Resende Corrêa; Eduardo Osório Senra; Eduardo Baudson Duarte; Fabyano A. C. Lopes; Micheline C. Silva; Peter Convey; Paulo E. A. S. Câmara; Luiz Henrique Rosa (Brazilian Journal of Microbiology, 2026)
We evaluated endolithic fungal diversity associated with rocks sampled at the polyextreme Brazilian São Pedro and São Paulo archipelago using a DNA amplicon metagenomics approach. We detected 808,547 fungal DNA reads grouped into 92 amplicon sequence variants (ASVs). The rocks sampled were geologically characterized as mylonitized peridotites, serpentinized peridotites, and carbonate-matrix sedimentary breccias. Ascomycota was the dominant phylum, followed by Basidiomycota , Mucoromycota , Mortierellomycota and Chytridiomycota . Hortaea werneckii , Cladosporium sp., Simplicillium sp., Blastobotrys serpentis , Penicillium sp., P. simplicissimum , Malassezia restricta , Ascomycota sp., Verrucariaceae sp., and Fungal sp. were the dominant assigned taxa. The endolithic assemblages displayed moderate to low diversity indices. Among the fungal community, only the dominant Fungal sp. occurred in all samples. The data obtained in our environmental DNA (eDNA) amplicon metagenomics approach suggest that the rocks of the isolated equatorial São Pedro and São Paulo archipelago host a complex fungal diversity, including taxa regarded to be cosmopolitan, extremophilic hypersaline and xerophilic, plant pathogens, and human/animal opportunistic pathogens. As eDNA studies do not confirm the presence of viable organisms or propagules, further research using culturing approaches is now required to develop strategies to recover these fungi for physiological, biogeochemical, genetic and potential biotechnological studies.

Lianas and trees 30-years after liana cutting and selective logging in the Amazon - Vitoria Duarte Derisso; Maria Tereza Grombone-Guaratini; Francis E. Putz; Rodrigo Costa Pinto; Iran Paz Pires; Edson Vidal (Forest Ecology and Management, 2026)

Geochemistry of BIF/chert and mafic rocks from the Archean Lamego gold deposit: Constraints on depositional model, metallogenetic and geotectonic implications - Vinícius Nogueira Duarte; Lydia Maria Lobato; Rosaline Cristina Figueiredo e Silva; Flávia Cristina Silveira Braga; Noreto Costa Sena; Breno de Souza Martins (Journal of South American Earth Sciences, 2026)

Anti-environmental political agendas, firearm deregulation and illegal hunting in Brazil - Hani R. El Bizri; Thais Queiroz Morcatty; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Kacie Henson; Camila Alvez Islas; Gabriel Favero Massocato; Arnaud L.J. Desbiez; João Vitor Campos-Silva; Daniel Zani La Laina; et al. (Biological Conservation, 2026)

Animal responses and physiological indicators of stress in late pregnant alpacas on cultivated pastures in the High Peruvian Andes - Diannett Benito López; Laura B. Gualdrón-Duarte; Rassiel Macedo Sucari; Guadalupe Orellana Ligas; Yemi Sanca Uscamayta; Feliciano Rivera Pachiño; Nancy F. Huanca-Marca; Francisco E. Franco; Rubén García-Ticllacuri; Joel Pacheco Curie; Bernardo Roque Huanca; Víctor M. Vélez-Marroquín; et al. (Tropical Animal Health and Production, 2026)

Resolving the Diet of Nesting Green Turtles in the Northeastern Red Sea - Hugo F. Mann; Natalie E. Wildermann; Chuancheng Fu; Hector Barrios-Garrido; Takahiro Shimada; Antonio Delgado-Huertas; Carlos M. Duarte (Estuaries and Coasts, 2026)
Stable isotope analysis of green turtle ( Chelonia mydas ) scutes provides insights into long-term dietary patterns (~ 6.5 years). We analysed δ¹³C and δ¹⁵N values from nesting turtles in the Red Sea and combined these with macrophyte isotope data from the literature. Bayesian mixing models estimated dietary contributions by habitat and taxa. Seagrass meadows were the dominant inferred carbon source, contributing 90.1 ± 4.7%, with seagrass taxa contributing 92.3 ± 3.8%. Among available sources, Cymodocea sp and Enhalus acoroides showed the highest estimated contributions (43.5 ± 13.1% and 24.0 ± 8.6%, respectively), although source overlap and literature-derived baselines limit species-level resolution. These results should therefore be interpreted as consistent with, rather than definitive evidence of, species-specific dietary dominance. Gaussian mixture modelling identified two foraging clusters: “Close” and “Distant.” Distant foragers travelled farther ( F = 67.44, P < 0.001) and were smaller ( F = 36.63, P < 0.001). δ¹⁵N differed between clusters ( F = 4.82, P = 0.034), while δ¹³C showed a non-significant trend ( F = 3.71, P = 0.061). Because isotope baselines were derived from literature, temporal and spatial mismatch constrains inference about current ecosystem condition. These findings are therefore hypothesis-generating and provide a foundation for future field-validated studies of trophic ecology in the Red Sea.

A global synthesis of ecosystem services records and their associations with marine and coastal habitats - Joana Martelo; Sandra A. Ferreira; Ronaldo Sousa; Sílvia B. Carvalho; Manuel Hidalgo; Henrique Cabral; Marina Dolbeth; Martin Lindegren; Ana Veríssimo; Anne E. Magurran; Bernardo Duarte; Sofia Henriques; et al. (Ecosystem Services, 2026)

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Pigmented fungi derived from hot and cold deserts ecosystems: taxonomy, genomic and biotechnological approach - Mayanne Karla da Silva; Rubens Correia da Silva; Beatriz Medeiros de Souza Melo; Thiago José Carvalho Cavalcante; Leonardo da Silva Santos; João Gabriel Pereira e Silva; Vannêssa Rodrigues Teles Maia; Monelly da Silva Bernardo; Kelvin da Silva Sousa; Averlane Vieira da Silva; Adeildo Júnior de Oliveira; Aline Cavalcanti de Queiroz; et al. (World Journal of Microbiology and Biotechnology, 2026)

Effects of high- and low-phenolic pea and field bean residues at contrasting doses on soil respiration, mineral N dynamics, microbial biomass, and subsequent barley growth - Rafael D. C. Duarte; Sandra Caul; Madeline E. Giles; Eric Paterson; Pietro P. M. Iannetta; Ana M. Gomes; Marta W. Vasconcelos (Plant and Soil, 2026)
Background and aims Legume residues are important organic inputs, but their effects depend on residue chemistry and application rate. This study examined how pea ( Pisum sativum ) and field bean ( Vicia faba ) residues with contrasting phytochemical compositions influenced soil functioning and subsequent barley growth, assessing how residue quality and dose shape soil responses. Methods A sandy loam soil was amended with residues from four legume genotypes with contrasting phytochemical profiles but similar C:N ratios, applied at low (5 t ha⁻ 1 ) and high (20 t ha⁻ 1 ) rates. Unamended and mineral fertilization treatments were included for comparison. Barley was then grown in a microcosm setup for 8 weeks, and soil CO₂ efflux, microbial biomass C, inorganic N dynamics, and plant biomass were assessed. Results High-dose applications substantially increased cumulative CO₂ emissions but led to reduced microbial biomass, lower nitrate availability, and significantly suppressed barley growth, particularly for high-phenolic genotypes. In contrast, low-dose low-phenolic residues increased microbial biomass, promoted nitrification, and supported barley growth comparable with mineral fertilizers. Phenolic-rich residues maintained higher ammonium levels and showed reduced microbial and plant responses, indicating inhibitory effects of certain phytochemicals on soil processes. Conclusion Residue impacts on soil processes and crop performance depend strongly on both phytochemical composition and application rate. Low-phenolic residues applied at moderate doses have positively impacted microbial functioning, nitrogen cycling, and barley biomass, whereas high doses, especially of high-phenolic material, were detrimental to microbial activity and plant growth. Integrating residue chemistry into nutrient management could enhance the sustainability of legume-based cropping systems.

Pathogens in the bay: environmental Staphylococcus saprophyticus strains mirror clinical counterparts in virulence, biofilm formation, antimicrobial resistance, pathogenicity, and phage susceptibility - Isabella Monteiro Carvalho; Erica Cristina Soares e Silva; Geovana Lacerda Rodrigues; Natállia Duarte dos Santos; Raienne Vitória da Silva Soares; Monalessa Fábia Pereira; Ciro César Rossi; Marcia Giambiagi-deMarval (Antonie van Leeuwenhoek, 2026)
Staphylococcus saprophyticus is a leading cause of urinary tract infections, yet little is known about its environmental reservoirs and traits outside clinical settings. This study aimed to compare clinical and environmental S. saprophyticus strains isolated from a polluted coastal ecosystem in Brazil, assessing their virulence-associated traits, antimicrobial resistance, biofilm formation, and susceptibility to bacteriophages. Forty strains (20 clinical, 20 environmental) were characterized using GTG 5 -PCR, virulence gene screening, antibiotic susceptibility testing, biofilm assays, exposure to sub-inhibitory concentrations of ciprofloxacin, Tenebrio molitor infection model, and phage activity tests. Genetic fingerprinting and virulence gene profiles revealed a high degree of similarity between environmental and clinical isolates, indicating the presence of shared virulence-associated determinants. Environmental strains exhibited resistance to multiple antibiotics and showed biofilm formation and larval survival patterns comparable to those observed for clinical isolates. Exposure to sub-inhibitory concentrations of ciprofloxacin increased biofilm formation in several strains. Bacteriophage CSF, originally isolated from swine farm effluent, displayed lytic and antibiofilm activity against a substantial proportion of the isolates. These findings highlight the presence of clinically relevant traits among environmental S. saprophyticus strains and underscore the importance of continued microbiological surveillance in anthropized aquatic environments.

Correction: Phytotoxicity and metal mobility in soils contaminated with mine tailings - Andressa Cristhy Buch; Maria Elizabeth Fernandes Correia; Júlia Carina Niemeyer; Douglas Brian Sims; Eduardo Duarte Marques; Krishna Kumar Yadav; Ahmad J. Obaidullah; Camila Rodrigues e Silva; Emmanoel Vieira da Silva-Filho (Environmental Geochemistry and Health, 2026)

Maternal chromium propionate supplementation in late gestation and its association with cow performance and skeletal muscle programming in beef calves - Emily A. Knapper; Luiza V. Kladt; Ivan I. Avalos-Rosario; Sarah E. Dean; Walmir Silva; Nicola V.L. Serão; Jerilyn E. Hergenreder; Elliot L. Neto; Katharine M. Wood; Michael A. Steele; Matheus P. Gionbelli; Marcio S. Duarte (Animal Feed Science and Technology, 2026)

Veterinary perspectives on biosecurity measures in small-scale farming systems across European countries: Results from a cross-national survey - F. Duarte; J. Prodanov-Radulović; B. Mehmedi; A. Piccirillo; M. Stukelj; E. Kldiashvili; V. Nedosekov; B. Milovanovic; N.D. Ayaz; R. Yildiz; S. Meling; I. Toftaker; et al. (Research in Veterinary Science, 2026)

From waste to resources: Integrating advanced oxidation and hydrochar production for potassium recovery and carbon retention - Jefferson E. Silveira; Jose L.S. Duarte; Alyson R. Ribeiro; Jose A. Casas; Juan A. Zazo (Bioresource Technology, 2026)

Phytotoxicity and metal mobility in soils contaminated with mine tailings - Andressa Cristhy Buch; Maria Elizabeth Fernandes Correia; Júlia Carina Niemeyer; Douglas Brian Sims; Eduardo Duarte Marques; Krishna Kumar Yadav; Ahmad J. Obaidullah; Camila Rodrigues e Silva; Emmanoel Vieira da Silva-Filho (Environmental Geochemistry and Health, 2026)
The consumption of vegetables is essential for human health. However, in regions affected by mining activities, this practice may pose serious risks due to potential heavy metal contamination at the soil–plant interface. This study evaluated the phytotoxicity and metal mobility in lettuce cultivated in mine tailing-contaminated soils after the Córrego do Feijão dam failure (Brumadinho, Minas Gerais, Brazil). The increase in soil metal concentrations negatively influenced morphological parameters such as root and shoot length, fresh biomass, germination, chlorophyll content, and the pattern and frequency of stomata on the leaf surface. Translocation factors of Fe, Ni, Mn, Cd, Cu, Pb, and Zn from roots to shoots of lettuce indicated significant risks to human health. In shoots, the concentrations of As, Cd, Pb, and Cu exceeded the maximum permissible limits for human consumption in lettuce and other leafy Asteraceae by up to 407-, 98-, 5,483-, and 28-fold, respectively. These results highlight the urgent need for mitigation, remediation, and protective strategies to safeguard human and animal health in mining regions, particularly where mining, agriculture, and livestock production coexist.

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Genomic, biological, and chemical studies of Streptomyces sp. LaBMicrA B280 isolated from the rhizosphere of Inga edulis Martius in the Amazon - Rafael de Souza Rodrigues; Antonia Queiroz Lima de Souza; Jania Lilia da Silva Bentes; Kamila Rangel Primo Fernandes; Felipe Moura Araújo da Silva; Maria de Fátima Oliveira Almeida; Rafael Pinto e Souza; Anderson Nogueira Barbosa; Fábio César Sousa Nogueira; Gabriel Reis Alves Carneiro; Ricardo de Melo Katak; Ivanildes dos Santos Bastos; et al. (Antonie van Leeuwenhoek, 2026)
In this study, we investigated the taxonomic identity and biotechnological potential of the actinobacterium Streptomyces sp. LaBMicrA B280, isolated from the rhizosphere of Inga edulis (Mart.). Our approach combined a phylogenomic approach, annotation of metabolic subsystems and biosynthetic gene clusters (BGCs), biological assays to assess antifungal, antimalarial, cytotoxic, and larvicidal activities, classical molecular networking analysis, and characterization of the major compound in the most active fraction (FR3). The digital DNA–DNA hybridization values, using the d2 (GGDC) and d4 (TYGS) formulas, average nucleotide identity, and average amino acid identity ( Streptomyces genus. Our genomic analysis revealed 39 BGCs, including the cluster responsible for pentamycin biosynthesis, 314 metabolic subsystems, and 24 gene categories. In the molecular networking analysis, pentamycin was the only compound identified. Biological assays with fraction FR3 at a concentration of 50 µg/mL showed 96.59% ± 0.03 and 72.39% ± 0.18 inhibition against Plasmodium falciparum strains W2 and 3D7, respectively, as well as 91.45% ± 0.55 cytotoxicity against the HEp-2 cancer cell line. Larvicidal activity assays demonstrated 100% efficacy against Aedes aegypti (FO) at 250 µg/mL after 48 h. Pentamycin, a known antifungal compound, was successfully isolated from the highly active FR3 fraction. These findings highlight that LaBMicrA B280 exhibits a broad biotechnological potential and represents a promising source of important secondary metabolites for future application.

Integrating elemental and total reflection X-ray spectral fingerprints with machine learning for advanced seafood traceability - Nuno M. Rodrigues; Vanessa F. Fonseca; Renato Mamede; Susanne E. Tanner; Bernardo Duarte; Sara Silva (Food Control, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Amazonian drought of 2023: Environmental conditions relevant to fishes - Ora E. Johannsson; Thiago L. Nascimento; Helen Agasild; Priit Zingel; Rafael M. Duarte; Gudrun de Boeck; Anne Cremazy; Jhonatan Mota da Silva; Carolyn Morris; Chris M. Wood; Adalberto L. Val (Journal of Fish Biology, 2026)
This paper provides a platform for the following studies within this Special Issue. ‘Ecophysiology of fishes in the two great tributaries of the Amazon in the Anthropocene’. It documents the water quality conditions and accompanying zooplankton community structure and biomass relative to fish health in the Rio Negro and Rio Solimões during the extreme drought of 2023. Our goals were to document conditions, compare them with historical data and assess their implications for the resident fishes. During the 2023 drought, fishes in the Rio Negro came under more pressure from environmental changes than fishes in the Rio Solimões. Habitats became smaller and less diverse than normally observed by the end of the annual drought in both rivers. In some areas, fishes experienced elevated temperatures and/or reduced oxygen especially in the floodplain lakes and shallower areas. In the Rio Negro, increases in total suspended solids (TSS) decreased the range of vision for resident fishes, which would have both protected them from predators and shielded their prey. The coincidence of higher temperatures and higher oxygen in the afternoon in the Rio Negro suggests that primary production still occurred in the shallower, lit surface waters. This would explain the presence of zooplankton near the water's surface. Predation was likely intense as the macro‐zooplankton were small, although, the effect of high temperatures on metabolic rates could also influence size. Cladoceran biomass showed a negative relationship with the mass of the 1.2−50 μm fraction of TSS. Higher TSS concentrations likely meant resuspension of sediments. Spectroscopic analysis showed that dissolved organic carbon (DOC) was more degraded than normal, and thus would have provided less protection against the effects of low pH on ionoregulation. Low pH and low conductivity put extreme stress on maintaining ion balance in the black waters. In the Rio Solimões, fish suffered less environmental change. Water temperature and oxygen concentrations were more moderate, although evidence suggests that temperature and conductivity have increased compared to historic data. The concentration of TSS was normal. The greatest change was a 200% to 300% increase in DOC, albeit the DOC was very degraded. This may have spurred the high biomass of bacteria which was out of balance with the other components of the microbial loop. The passage of energy from bacteria to higher zooplankton trophic levels worked efficiently in the Rio Negro but not the Rio Solimões. This study allows a better understanding of the stresses on the fish community in these adverse conditions and the implications for their future.

Joint effects of elevated copper and temperature in juvenile Tambaqui exposed in black and white waters of the Amazon - Anne Crémazy; Carolyn Morris; Susana Braz‐Mota; Chris M. Wood; Rafael M. Duarte; Ora E. Johannsson; Adalberto L. Val (Journal of Fish Biology, 2026)
This study aimed to investigate how exposure to elevated water temperature and metal concentration jointly affect the physiology of Amazonian fish. Aboard a research vessel in the Amazon, we evaluated the effects of water temperature (river T°C at 31.5°C and a + 4°C increase to 35.5°C) and of 3‐h copper (Cu) exposure (up to 600 μg/L) in juvenile Tambaqui ( Colossoma macropomum ) exposed in freshly collected Rio Negro (‘black water’) and Rio Solimões (‘white water’) waters. In Cu‐free water, the +4°C raise accelerated physiological Na + influx and efflux rates, but only in Rio Negro water. Temperature had no effects on the other physiological fluxes (Cl − , K + and ammonia fluxes). Cu exposure led to net losses of Na + (via increased efflux), Cl − and K + and decrease in acute upper thermal tolerance (CT max ). These Cu effects were more prominent in Rio Negro water, where Cu bioavailability was the greatest. The +4°C change had no effect on gill Cu accumulation and, overall, there was limited evidence that warming worsened Cu‐induced ionoregulatory disturbances. However, in Rio Negro, as Cu and heat both separately promoted Na + net losses, fish Na + balance was the most compromised in the presence of the two stressors. Altogether, the impaired thermotolerance and ionoregulation under combined Cu and heat exposures suggest a cumulative physiological interaction between two stressors that are increasing threats to the Amazon basin.

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Assessing Prokaryotic Benthic Communities in the Red Sea - Christopher A. Hempel; Larissa Frühe; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Diego E. Rivera Rosas; Amal A. Bajaffer; Wajitha J. R. M. Sait; Alexandra Steckbauer; Taiba Alamoudi; Jacqueline V. Alva García; Shannon G. Klein; et al. (Environmental Microbiology, 2026)
Marine sediments host diverse benthic prokaryotic communities that are integral to global biogeochemical cycles. However, the spatial distribution and environmental drivers of these communities, particularly in unique environments like the Red Sea, remain largely underexplored. In this study, we examine benthic prokaryotic communities sampled during the Red Sea Decade Expedition (RSDE) using 16S rRNA gene sequencing across five major regions along the Red Sea's latitudinal gradient and three depth strata. Our findings reveal distinct biogeographical patterns shaped by depth, latitude, and oxygen availability, with clear shifts in microbial community composition across the epibenthic, mesobenthic and bathybenthic zones. Bathybenthic communities exhibited consistently low levels of OTU richness throughout the Red Sea, likely due to uniform niche environmental conditions at depth, while shallower communities showed higher OTU richness towards the Southern Red Sea. The southern region harboured higher relative abundances of Chloroflexi and reduced relative abundances of Proteobacteria and Acidobacteriota relative to the northern regions. Extreme environments, such as the Atlantis II brine pool, supported specialised microbial communities likely adapted to extreme conditions like hypersalinity. This study established a critical baseline for understanding the responses of marine microbial communities to climate change and their roles in biogeochemical processes.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Natural regeneration of native woodlands in drylands subjected to disturbances: A basis for their ecological restoration - Yamila J. Duarte; Bárbara Guida-Johnson; Leandro M. Alvarez; María Agustina Aranda; Brian Leonardo A. Rios; Pablo E. Villagra (Forest Ecology and Management, 2025)

Occurrence of Listeria spp. and Listeria monocytogenes in half-carcasses, meat cuts, equipment, and the environment of bovine slaughterhouses in Brazil - Leonardo França; Ursula Nunes Rauecker; Daniel Lucino Silva dos Santos; Naara Aparecida Almeida; Clarice Gebara; Cristiano Sales Prado; Valéria Quintana Cavicchioli; Moacir Evandro Lage; Francine Oliveira Duarte; Cíntia Silva Minafra e Rezende; Ana Maria de Souza Almeida; Iolanda Aparecida Nunes (Research in Veterinary Science, 2025)

Insight into polycyclic aromatic hydrocarbons removal using novel surfactant-clay hybrid material - Israel G.A. Funes; Luciano E. Duarte; Telma B. Musso; Luciano Carlos; María E. Parolo (Applied Clay Science, 2025)

Global Patterns and Drivers of Seagrass Biomass, Net Primary Production and Meadow Structure - Nicole R. Foster; Enric Gomis; Diana I. Montemayor; Simone Strydom; Miguel Angel Mateo; Eduard Serrano; Aurora M. Ricart; Martin Dahl; Ines Mazarrasa; Paulina Cisternas; Harry Whiteley; Elliott J. Bates; et al. (Journal of Biogeography, 2025)
Aim We decipher global patterns in seagrass growth and structure to advance seagrass science, facilitate multidisciplinary research, and promote effective management strategies and policy development for seagrass habitats. Location: Global. Time period: 1975 to 2024. Major taxa studied: Seagrasses—marine angiosperms. Methods A global data set on seagrass total biomass, total net primary productivity (NPP), shoot density, and percent cover was compiled across 11 genera. We tested how these variables change across seagrass genera, life‐history strategy, and geographic location; and then modelled the environmental drivers (temperature, nutrients, light availability) of the patterns observed. Results The mean (±SE) total biomass of seagrasses globally was estimated at 340 ± 10 g DW m −2 and total NPP was estimated at 5.4 ± 0.4 g DW m −2 d −1 . Mean shoot density across all genera was 1,780 ± 67 shoots m −2 and percent cover was 42% ± 1%. Persistent genera showed the highest total biomass followed by opportunistic then colonising genera, whereas shoot density was higher for colonising than persistent, which had the highest percent cover. Latitudinal and bioregional patterns were identified for some genera and were mostly driven by genus‐specific traits, followed by localised environmental factors. Main Conclusions Trends in seagrass meadow ecology were largely influenced by seagrass genera and their life‐history strategy, with localised environmental factors, such as temperature and nutrients, also playing a role. Global estimates of seagrass biomass and NPP were 2‐times higher than previously reported. Seagrass life‐history strategies modulate the trade‐offs between NPP and biomass to thrive in specific habitats. This study provides the most updated global synthesis of patterns in seagrass growth and structure.

Assessing the impact of urbanization on wetland bird communities in Chilean Mediterranean coast - Pablo Díaz-Siefer; Isidora Duarte; Victoria Madrid; Natalia Olmos-Moya; Francisco E. Fontúrbel; Juan L. Celis-Diez (Urban Ecosystems, 2025)

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Carbon footprint calculator for the Portuguese textile and clothing industry: development, application and validation - C. Duarte; J. V. Ferreira; I. P. L. Brás; M. E. F. Silva (International Journal of Environmental Science and Technology, 2025)
This study aimed to develop, implement, and validate a carbon footprint (CF) calculator to estimate greenhouse gas (GHG) emissions generated by Portugal´s Textile and Clothing Sector (TCS). To achieve this, the GHG Protocol and life cycle assessment (LCA) methodology were applied to develop the CF and analyse two textile and clothing companies (A and B). Validation was conducted using a self-assessment method that employed 2 online calculators and a LCA software. The CF calculator enables the quantification of the 3 scopes of GHG emissions. Scope 1 includes direct emissions from sources that are owned or controlled by the company, such as on-site energy, transportation of raw materials, finished products and personnel, as well as water usage. Scope 2 comprises indirect emissions from the use of purchased energy and Scope 3 includes emissions that occur across the supply chain, such as public water usage, wastewater, transportation, employee business travel, waste disposal and the end-of-life treatment of sold products. Avoided emissions and carbon offsetting measures and carbon sequestration strategies, were included. For Company A, energy consumption was the largest contributor to the CF, accounting for 76% of the contributions. In Company B, the waste component had the greatest impact on the CF, accounted for 38% of the contributions. In the validation process, the electricity and fuel consumption components yielded values that are consistent with those from other calculators. The calculator is a tool that TCS companies can use to quantify their emissions and define measures to reduce or offset their CF.

From past to present: Shifting landscape drivers of dung beetle functional and phylogenetic diversity in a tropical reserve - José D. Rivera-Duarte; Renato P. Salomão; Eduardo Ulises Castillo-Pérez; Juan José Von Thaden; Alejandro Espinosa de los Monteros; Mario E. Favila (Journal of Environmental Management, 2025)

The socio-environmental observatory: an information platform for transparency, participatory governance, and environmental justice in the Sonora River Basin, Mexico - Agustin Robles-Morua; Laurent Avila-Chauvet; Rolando E. Díaz-Caravantes; Efraín Vizuete-Jaramillo; America Lutz-Ley; Hector Duarte-Tagles; Luis Franco-Garza; Patricia Velarde (Socio-Ecological Practice Research, 2025)

Molecular modeling of a novel butane-substituted chalcone: from synthesis to comprehensive electron density analysis - Aécio V. B. Oliveira; Vitor S. Duarte; Renata Layse. G. de Paula; Jaqueline E. Queiroz; Gilberto L. B. de Aquino; Hamilton B. Napolitano; Ademir J. Camargo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Simple distillation combined with advanced oxidation as a promising strategy to treat and reduce the phytotoxicity of landfill leachate - Siara Silvestri; Ágatha E. Duarte; Gabriela G. Bueno; Guilherme V. Ferreira; Maria Angélica O. Linton; Elvis Carissimi; André R. Fajardo (Journal of Environmental Management, 2025)

Socioenvironmental impacts of the Belo Monte hydroelectric power plant as revealed by Indigenous and ribeirinho monitoring - Josiel Jacinto Pereira Juruna; Raimundo da Cruz e Silva; Orcylene Barbosa dos Reis; Amildon Moura Assunção; Anderson Sampaio da Silva; Helio Bezerra da Silva; Jailson Jacinto Pereira Juruna; Josimary Abreu Nunes; Micaele Souza Santos Kleme; Paulo Passos Ferreira; Ronald Txakui Viana da Silva Juruna; Rosilene Sousa dos Santos; et al. (Conservation Biology, 2025)
Hydroelectric dams, once seen as clean and renewable energy sources, have been the subject of extensive research, particularly concerning their socioenvironmental impacts. The Belo Monte hydroelectric power plant (HPP) relies on the operation of 2 dams that divert water from a 130‐km stretch of the Xingu River to generate energy. The dam has disrupted the seasonal flooding cycle (flood pulse) along the Volta Grande do Xingu (VGX) and created a reduced discharge condition analogous to a prolonged and extreme dry season in the watershed. Before the Belo Monte HPP, local communities relied on the highly diverse and abundant fish assemblage supported by seasonal flooding of the ecosystem. Local VGX residents sought partnerships and established the Independent Territorial Environmental Monitoring Program (MATI‐VGX). Through this program, locals monitored fish spawning sites and fishing dynamics. This monitoring complemented and quantified local communities’ perceptions about the environmental impacts caused by the Belo Monte HPP. The HPP was associated with a water discharge shortage that critically undermined the river's capacity to sustain vital ecosystem processes that support local people's lives. Drastic transformations of traditional lifestyles, shifts in fishing practices, and a significant decline in fishing yield occurred that jeopardized food sovereignty and security. The Belo Monte HPP environmental licensing process ignored local ecological knowledge and the vital links among the river's flood pulse, the aquatic and seasonally flooded ecosystems, and the traditional lifestyles of VGX residents. To ensure the ecological sustainability of the VGX, the Belo Monte HPP operation needs to change to support key spawning areas, maintain water discharge, avoid short‐term water fluctuations, and emulate natural interannual discharge variability to mitigate flood pulse disruption. Local ecological knowledge should never be ignored in projects where local communities are the most affected. These communities should be central in decision‐making regarding socioenvironmental impact assessment, mitigation, and monitoring.

Evaluation of different external neutron sources for a hybrid system based on the SEALER reactor - João P.C. Melo; Lucas V.G. Chaves; Samuel V.F. Silva; Jefferson Duarte; Karytha M.S. Corrêa; Natália G.P.L. Oliveira; José Cassimiro; Carlos E. Velasquez; Clarysson A.M. da Silva; Claubia Pereira (Annals of Nuclear Energy, 2025)

Ingestive behaviour, performance, and methane emissions of pregnant alpacas grazing cultivated pastures in the high Peruvian Andes - Laura B. Gualdrón-Duarte; Cecilia Loza; José I. Gere; Nancy F. Huanca-Marca; Francisco E. Franco; Yemi Sanca Uscamayta; Rubén García‐Ticllacuri; Guadalupe Orellana Ligas; Diannett Benito López; Feliciano Rivera Pachiño; Juan E. Moscoso-Muñoz; Medardo A. Díaz-Céspedes; et al. (Livestock Science, 2025)

Testis transcriptomic analyses reveal the effects of an algae feed on sperm quality in Senegalese sole during the breeding season - F. Félix; C. Raposo de Magalhães; C. Marrero-Alemán; D. Duarte; P. Parente; E. Fatsini; C.C.V. Oliveira; E. Cabrita (Aquaculture, 2025)

Impact of monensin, virginiamycin, trace minerals, and yeast combination on animal performance, carcass and meat characteristics of finishing feedlot bulls fed high grain diet - Vanessa Duarte; Fabio Garcia Ribeiro; Aylle Medeiros Matos; Rodolpho Martin do Prado; Luiz Fernando Costa e Silva; Venício Macedo Carvalho; Vicente Alfonso Díaz Ávila; Melina Aparecida Plastina Cardoso; Ivanor Nunes do Prado (Tropical Animal Health and Production, 2025)

Particle‐Associated Bacterioplankton Communities Across the Red Sea - Larissa Frühe; Shannon G. Klein; Carlos Angulo‐Preckler; Anastasiia Martynova; Taiba Alamoudi; Jacqueline V. Alva García; Silvia Arossa; Jessica Breavington; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Anieka J. Parry; et al. (Environmental Microbiology, 2025)
Pelagic particle‐associated bacterioplankton play crucial roles in marine ecosystems, influencing biogeochemical cycling and ecosystem functioning. However, their diversity, composition, and dynamics remain poorly understood, particularly in unique environments such as the Red Sea. In this study, we employed eDNA metabarcoding to comprehensively characterise bacterioplankton communities associated with pelagic particles in a three‐dimensional assessment spanning depths from the surface to a depth of 2300 m along the full length of the eastern Red Sea within the exclusive economic zone of the Kingdom of Saudi Arabia. Our results reveal a diverse assemblage of taxa, with Pseudomonadota, Cyanobacteriota, and Planctomycetota being the dominant phyla. We identified pronounced spatial variability in community composition among five major Red Sea geographical regions, with a third of all amplicon sequence variants being unique to the Southern Red Sea in contrast to a relatively homogenous distribution along the water column depth gradient. Our findings contribute to a deeper understanding of microbial ecology in the Red Sea and provide valuable insights into the factors governing pelagic particle‐associated bacterioplankton communities in this basin.

Anthocyanins stabilization of Hibiscus sabdariffa extract with sepiolite: Analytical and reactive force fields approaches - Ana S. Márquez-Rodríguez; Arasay Carrión; Felipe Trejo; Hilda E. Esparza-Ponce; José M. Nápoles-Duarte; María L. Ballinas-Casarrubias; Luis E. Fuentes-Cobas; Erika Salas; Juan P. Palomares-Báez; María E. Fuentes-Montero (Sustainable Chemistry and Pharmacy, 2024)

Exploring the potential of Desert Rose fibers (Adenium obesum) for the remediation of oil-contaminated sites - Bianca Alice Santos de Godoy; Davisson Costa Galindo; Eduardo Jorge Fonseca; Carmem Lúcia de Paiva e Silva Zanta; Laís Farias Azevedo de Magalhães Oliveira; José Leandro da Silva Duarte; Vanderson Bernardo; Leonardo Mendonça Tenório de Magalhães Oliveira (Journal of Water Process Engineering, 2024)

Enhanced photo-oxidation of hormones in water using biomass waste-derived hydrochar composites as photocatalysts - Siara Silvestri; Ágatha E. Duarte; Gabriela G. Bueno; Elvis Carissimi; André R. Fajardo (Bioresource Technology Reports, 2024)

Expression of Dystrophin Dp71 Splice Variants Is Temporally Regulated During Rodent Brain Development - Mayram González-Reyes; Jorge Aragón; Alejandra Sánchez-Trujillo; Griselda Rodríguez-Martínez; Kevin Duarte; Evangelia Eleftheriou; Jean-Vianney Barnier; Delphine Naquin; Claude Thermes; José Romo-Yáñez; Jérome E. Roger; Alvaro Rendon; et al. (Molecular Neurobiology, 2024)
Dystrophin Dp71 is the major product of the Duchenne muscular dystrophy ( DMD ) gene in the brain, and its loss in DMD patients and mouse models leads to cognitive impairments. Dp71 is expressed as a range of proteins generated by alternative splicing of exons 71 to 74 and 78, classified in the main Dp71d and Dp71f groups that contain specific C-terminal ends. However, it is unknown whether each isoform has a specific role in distinct cell types, brain regions, and/or stages of brain development. In the present study, we characterized the expression of Dp71 isoforms during fetal (E10.5, E15.5) and postnatal (P1, P7, P14, P21 and P60) mouse and rat brain development. We finely quantified the expression of several Dp71 transcripts by RT-PCR and cloning assays in samples from whole-brain and distinct brain structures. The following Dp71 transcripts were detected: Dp71d, Dp71d ∆71 , Dp71d ∆74 , Dp71d ∆71,74 , Dp71d ∆71−74 , Dp71f, Dp71f ∆71 , Dp71f ∆74 , Dp71f ∆71,74 , and Dp71f Δ71−74 . We found that the Dp71f isoform is the main transcript expressed at E10.5 (> 80%), while its expression is then progressively reduced and replaced by the expression of isoforms of the Dp71d group from E15.5 to postnatal and adult ages. This major finding was confirmed by third-generation nanopore sequencing. In addition, we found that the level of expression of specific Dp71 isoforms varies as a function of postnatal stages and brain structure. Our results suggest that Dp71 isoforms have different and complementary roles during embryonic and postnatal brain development, likely taking part in a variety of maturation processes in distinct cell types.

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Exposing illegal hunting and wildlife depletion in the world's largest tropical country through social media data - Hani R. El Bizri; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Lauren Coad; Thais Queiroz Morcatty; Gabriel Favero Massocato; Arnaud L. J. Desbiez; João Vitor Campos‐Silva; Daniel Zani La Laina; José Maurício Barbanti Duarte; et al. (Conservation Biology, 2024)
Globally, illegal sport hunting can threaten prey populations when unregulated. Due to its covert nature, illegal sport hunting poses challenges for data collection, hindering efforts to understand the full extent of its impacts. We gathered social media data to analyze patterns of illegal sport hunting and wildlife depletion across Brazil. We collected data for 2 years (2018–2020) across 5 Facebook groups containing posts depicting pictures of illegal sport hunting events of native fauna. We described and mapped these hunting events by detailing the number of hunters involved, the number of species, the mean body mass of individuals, and the number and biomass of individuals hunted per unit area, stratified by Brazilian biome. We also examined the effects of defaunation on hunting yield and composition via regression models, rank–abundance curves, and spatial interpolation. We detected 2046 illegal sport hunting posts portraying the hunting of 4658 animals (∼29 t of undressed meat) across all 27 states and 6 natural biomes of Brazil. Of 157 native species targeted by hunters, 19 are currently threatened with extinction. We estimated that 1414 hunters extracted 3251 kg/million km 2 . Some areas exhibited more pronounced wildlife depletion, in particular the Atlantic Forest and Caatinga biomes. In these areas, there was a shift from large mammals and reptiles to small birds as the main targeted taxa, and biomass extracted per hunting event and mean body mass across all taxonomic groups were lower than in other areas. Our results highlight that illegal sport hunting adds to the pressures of subsistence hunting and the wild meat trade on Brazil's wildlife populations. Enhanced surveillance efforts are needed to reduce illegal sport hunting levels and to develop well‐managed sustainable sport hunting programs. These can support wildlife conservation and offer incentives for local communities to oversee designated sport hunting areas.

Allelopathic effects of cyanotoxins on the physiological responses of Chlorella vulgaris - Maria Virgínia da Conceição Albuquerque; Railson de Oliveira Ramos; Maria Célia Cavalcante de Paula e Silva; Roberta Milena Moura Rodrigues; Valderi Duarte Leite; Wilton Silva Lopes (Toxicon, 2024)

Comprehensive DNA metabarcoding-based detection of non-indigenous invertebrates in recreational marinas through a multi-substrate approach - Ana S. Lavrador; Fábio G. Amaral; Jorge Moutinho; Pedro E. Vieira; Filipe O. Costa; Sofia Duarte (Marine Environmental Research, 2024)

Dietary guanidinoacetic acid as arginine spare molecule for beef cows at late gestation: Effects on cow’s performance and metabolism, and offspring growth and development - L.C.O. Sousa; E.M.A. Matos; M.M. Santos; E. Detmann; C.B. Sampaio; Y.F.R. Sancler-Silva; L.N. Rennó; N.V.L. Serão; P.V.R. Paulino; T.L. Resende; M.P. Gionbelli; M.S. Duarte (Animal Feed Science and Technology, 2024)

In vitro antiproliferative effects of Vatairea macrocarpa (Benth.) Ducke lectin on human tumor cell lines and in vivo evaluation of its toxicity in Drosophila melanogaster - Adrielle R. Costa; Antonio M.O. Santos; Francisco S. Barreto; Pedro M.S. Costa; Renato R. Roma; Bruno A.M. Rocha; Carlos V.B. Oliveira; Antonia E. Duarte; Claudia Pessoa; Claudener S. Teixeira (Food and Chemical Toxicology, 2024)

Bacterial septicemia and herpesvirus infection in Antarctic fur seals (Arctocephalus gazella) stranded in the São Paulo coast, Brazil - Aricia Duarte-Benvenuto; A. M. Sánchez-Sarmiento; A. C. Ewbank; R. Zamana-Ramblas; S. Costa-Silva; N. Silvestre; T. Faita; L. B. Keid; R. M. Soares; C. F. Pessi; J. R. Sabbadini; M. F. Borges; et al. (Veterinary Research Communications, 2024)
In August 2021, two juvenile male Antarctic fur seals ( Arctocephalus gazella ) stranded in the southeastern Brazilian coast and were referred to rehabilitation centers. The animals presented increased body temperature, prostration, respiratory distress and despite treatment died. A necropsy following a standardized protocol was performed, and formalin-fixed tissues were processed for microscopic examination. Samples were screened for morbillivirus, herpesvirus, and Brucella spp. by molecular analyses (PCR, RT-PCR). Bacteriological culture was performed in samples collected from the lungs, trachea, and lymph nodes of both cases. The main histopathologic findings were of infectious nature, including multifocal necrotizing and fibrinous mixed interstitial pneumonia, bronchiolitis, and bronchitis, with intralesional myriad bacteria associated with vascular fibrinoid necrosis. Pseudomonas aeruginosa was isolated from tracheal and lung swabs of Case 1, and Klebsiella oxytoca was found in nostril swabs, tracheobronchial lymph nodes, and lung of Case 2. Gammaherpesvirus infection was detected in both cases, and the sequences retrieved were classified into the genus Percavirus . All tested samples were PCR-negative for Brucella spp. and morbillivirus. We hypothesize that the deficient immunological status in association with starvation predisposed the reactivation of herpesvirus and secondary bacterial co-infections. To the authors’ knowledge, this is the first molecular detection of herpesvirus in an Antarctic pinniped. These findings reinforce that Otariid gammaherpesvirus circulating in the Southern Hemisphere are likely endemic in the Arctocephalus genus. This report contributes to the current knowledge of health aspects affecting wild pinnipeds, especially in the poorly studied Antarctic species.

Collaborative action between noradrenergic and serotoninergic systems in peripheral antinociception in mice - Danielle Diniz Aguiar; Cristina da Costa Oliveira; Júlia Alvarenga Petrocchi; Marina Gomes Miranda E Castor; Andrea Castro Perez; Igor Dimitri Gama Duarte; Thiago Roberto Lima Romero (Journal of Biosciences, 2024)

Assessment of groundwater quality from monitoring wells in an area occupied by a cemetery in South Brazil - Gabriel D’ávila Fernandes; Willian Fernando de Borba; Paula Dalla Vecchia; Sérgio Roberto Mortari; Fábio Andrei Duarte; Pedro Daniel da Cunha Kemerich; Éricklis Edson Boito de Souza; José Luiz Silvério da Silva; Milene Priebe e Silva; Mateus Guimarães da Silva; Joao Pedro Berton Wissmann (Arabian Journal of Geosciences, 2024)

Seismic stratigraphy and sediment cores reveal lake-level fluctuations in Lake Iznik (NW Turkey) over the past ∼70 ka - R. Gastineau; F.S. Anselmetti; S.C. Fabbri; P. Sabatier; P. Roeser; S. Gündüz; M. Şahin; E. Duarte; W. Rapuc; A.C. Gebhardt; S.O. Franz; F. Niessen; et al. (Sedimentary Geology, 2024)

Do carcass traits influence consumer perception of pork eating quality? - Dante T. Valente Junior; Ira B. Mandell; Benjamin M. Bohrer; Justice B. Dorleku; Cheryl P. Campbell; Tadeu E. Silva; Edenio Detmann; Alysson Saraiva; Manuel Juárez; Marcio S. Duarte (Meat Science, 2024)

Rapid diversification of grey mangroves ( Avicennia marina ) driven by geographic isolation and extreme environmental conditions in the Arabian Peninsula - Guillermo Friis; Edward G. Smith; Catherine E. Lovelock; Alejandra Ortega; Alyssa Marshell; Carlos M. Duarte; John A. Burt (Molecular Ecology, 2024)
Biological systems occurring in ecologically heterogeneous and spatially discontinuous habitats provide an ideal opportunity to investigate the relative roles of neutral and selective factors in driving lineage diversification. The grey mangroves ( Avicennia marina ) of Arabia occur at the northern edge of the species' range and are subject to variable, often extreme, environmental conditions, as well as historic large fluctuations in habitat availability and connectivity resulting from Quaternary glacial cycles. Here, we analyse fully sequenced genomes sampled from 19 locations across the Red Sea, the Arabian Sea and the Persian/Arabian Gulf (PAG) to reconstruct the evolutionary history of the species in the region and to identify adaptive mechanisms of lineage diversification. Population structure and phylogenetic analyses revealed marked genetic structure correlating with geographic distance and highly supported clades among and within the seas surrounding the Arabian Peninsula. Demographic modelling showed times of divergence consistent with recent periods of geographic isolation and low marine connectivity during glaciations, suggesting the presence of (cryptic) glacial refugia in the Red Sea and the PAG. Significant migration was detected within the Red Sea and the PAG, and across the Strait of Hormuz to the Arabian Sea, suggesting gene flow upon secondary contact among populations. Genetic‐environment association analyses revealed high levels of adaptive divergence and detected signs of multi‐loci local adaptation driven by temperature extremes and hypersalinity. These results support a process of rapid diversification resulting from the combined effects of historical factors and ecological selection and reveal mangrove peripheral environments as relevant drivers of lineage diversity.

Modeling of soil organic matter using Sentinel-1 SAR and partial least squares (PLS) regression - Miqueias Lima Duarte; Darllan Collins da Cunha e Silva; Ricardo Luís Barbosa; Roberto Wagner Lourenço (Arabian Journal of Geosciences, 2024)

Cues of uncommon food habits within dung beetles: Notes from a seasonally dry tropical forest in South America - Luis Javier Fuentes-Jacques; Renato Portela Salomão; Jose D. Rivera-Duarte; Leonardo Vilas-Bôas M.P. De Cerqueira; Mario E. Favila (Journal of Arid Environments, 2023)

APGW/AKH Precursor from Rotifer Brachionus plicatilis and the DNA Loss Model Explain Evolutionary Trends of the Neuropeptide LWamide, APGWamide, RPCH, AKH, ACP, CRZ, and GnRH Families - Cristian E. Cadena-Caballero; Nestor Munive-Argüelles; Lina M. Vera-Cala; Carlos Barrios-Hernandez; Ruben O. Duarte-Bernal; Viviana L. Ayus-Ortiz; Luis A. Pardo-Díaz; Mayra Agudelo-Rodríguez; Lola X. Bautista-Rozo; Laura R. Jimenez-Gutierrez; Francisco Martinez-Perez (Journal of Molecular Evolution, 2023)
In the year 2002, DNA loss model (DNA-LM) postulated that neuropeptide genes to emerged through codons loss via the repair of damaged DNA from ancestral gene namely Neuropeptide Precursor Predictive ( NPP ), which organization correspond two or more neuropeptides precursors evolutive related. The DNA-LM was elaborated according to amino acids homology among LWamide, APGWamide, red pigment-concentrating hormone (RPCH), adipokinetic hormones (AKHs) and in silico APGW/RPCH NPP APGW/AKH NPP were proposed. With the above principle, it was proposed the evolution of corazonin (CRZ), gonadotropin-releasing hormone (GnRH), AKH, and AKH/CRZ (ACP), but any NPP never was considered. However, the evolutive relation via DNA-LM among these neuropeptides precursors not has been established yet. Therefore, the transcriptomes from crabs Callinectes toxotes and Callinectes arcuatus were used to characterized ACP and partial CRZ precursors, respectively. BLAST alignment with APGW/RPCH NPP and APGW/AKH NPP allow identified similar NPP in the rotifer Brachionus plicatilis and other invertebrates. Moreover, three bioinformatics algorithms and manual verification were used to purify 13,778 sequences, generating a database with 719 neuropeptide precursors. Phylogenetic trees with the DNA-LM parameters showed that some ACP, CRZ, AKH2 and two NPP share nodes with GnRH from vertebrates and some of this neuropeptide had nodes in invertebrates. Whereas the phylogenetic tree with standard parameters do not showed previous node pattern. Robinson-Foulds metric corroborates the differences among phylogenetic trees. Homology relationship showed four putative orthogroups; AKH4, CRZ, and protostomes GnRH had individual group. This is the first demonstration of NPP in species and would explain the evolution neuropeptide families by the DNA-LM.

Green roofs are effective in cooling and mitigating urban heat islands to improve human thermal comfort - Taize Calvacante Santana; Cristiane Guiselini; Abelardo Antônio de Assunção Montenegro; Héliton Pandorfi; Rodes Angelo Batista da Silva; Renan da Silva e Silva; Pedro Henrique Dias Batista; Sávio Duarte Lopes Cavalcanti; Nicoly Farias Gomes; Marcos Vinícius da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim (Modeling Earth Systems and Environment, 2023)

A common variant close to the “tripwire” linker region of NLRP1 contributes to severe COVID-19 - Vinicius N. C. Leal; Leandro M. Paulino; Raylane A. G. Cambui; Thiago G. Zupelli; Suemy M. Yamada; Leonardo A. T. Oliveira; Valéria de F. Dutra; Carolina B. Bub; Araci M. Sakashita; Ana Paula H. Yokoyama; José M. Kutner; Camila A. Vieira; et al. (Inflammation Research, 2023)

Cactus–sorghum intercropping combined with management interventions of planting density, row orientation and nitrogen fertilisation can optimise water use in dry regions - Thieres George Freire da Silva; Rômulo Sátiro de Medeiros; Francisco Dirceu Duarte Arraes; Clóvis Manoel Carvalho Ramos; George do Nascimento Araújo Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; Cleber Pereira Alves; Fleming Sena Campos; Marcos Vinícius da Silva; José Edson Florentino de Morais; Carlos André Alves de Souza; Sérvulo Mercier Siqueira e Silva; et al. (Science of The Total Environment, 2023)

Subsistence swine farming: seroprevalence and risk factors associated with Lawsonia intracellularis infection in the state of Minas Gerais Brazil in 2016 - J. C. R. Barbosa; R. R. Nicolino; M. P. Gabardo; J. P. M. Gonçalves; M. E. Suarez-Duarte; R. P. Laub; A. G. S. Daniel; G. H. S. Mariano; C. M. Costa; P. A. Correia; M. D. Araújo; R. M. C. Guedes (Tropical Animal Health and Production, 2023)

Effects of fire regime on the bird community in an Amazonian savanna - Laís Araújo Coelho; Camila Duarte Ritter; Albertina Pimentel Lima; Renato Cintra; William E. Magnusson; Tânia Margarete Sanaiotti (Biodiversity and Conservation, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Changes in the surface water quality of a tropical watershed in the southeastern amazon due to the environmental impacts of artisanal mining - Gabriel Negreiros Salomão; Roberto Dall’Agnol; Prafulla Kumar Sahoo; Gabriel Soares de Almeida; Rafael Tarantino Amarante; Leiliane Bozzi Zeferino; João Paulo Nobre Lopes; Pedro Walfir Martins e Souza Filho; Normara Yane Mar da Costa; José Tasso Felix Guimarães; Marcio Sousa da Silva; Gabriel Caixeta Martins; et al. (Environmental Pollution, 2023)

Phytochemical analysis, in vitro antioxidant and anticholinesterase activities of Solanum paniculatum L. and an in-silico test with the AChE enzyme - João Paulo Rodrigues da Silva; Adriane da Cunha Rios Aragão; Ronaldo dos Santos Sousa Junior; Clara Andrezza Crisóstomo Bezerra Costa; Orlando Francisco da Silva Moura; Thaís Danyelle Santos Araújo; Durcilene Alves da Silva; Antonio Rodrigues da Silva Neto; Kessia da Costa Silva; Tatiana de Oliveira Lopes; Penina Sousa Mourão; Lorena Thayla Nascimento e Sousa; et al. (South African Journal of Botany, 2023)

Green Nanobioinsecticide of a Brazilian endemic plant for the Aedes aegypti control - V.C.R. Viana; F.P. Machado; R. Esteves; J.A.D. Duarte; J.J.S. Enríquez; M.L.M. Campaz; E.E. Oliveira; M.G. Santos; E. Ricci-Junior; B.M. Ruppelt; L. Rocha (Sustainable Chemistry and Pharmacy, 2023)

Quantifying blue carbon stocks and the role of protected areas to conserve coastal wetlands - Micheli Duarte de Paula Costa; Maria Fernanda Adame; Catherine V. Bryant; Jack Hill; Jeffrey J. Kelleway; Catherine E. Lovelock; Anne Ola; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Nathan Waltham; Paul H. York; et al. (Science of The Total Environment, 2023)

Cryopreservation of mature zygotic embryos, shoot bud regeneration, and field establishment of Pinus elliottii var. elliottii x Pinus caribaea var. hondurensis in vitro-derived plants - Lilian P. E. Ayala; Claudia V. Luna; Elsa A. Brugnoli; Fabiana D. Espasandin; María J. Duarte; Ana M. González; María E. Gauchat; Paloma Moncaleán Guillén; Pedro A. Sansberro (Trees, 2023)

Magnetic MgAl-LDH for Adsorptive Removal of Malachite Green from Water - Ícaro Mychel Gomes Leite de Sá; Ivis de Melo Agra; Kleber Jean dos Santos Leite; Laís Farias Azevedo de Magalhães Oliveira; Eduardo Jorge da Silva Fonseca; Leonardo Mendonça Tenório de Magalh Oliveira; Carmem Lúcia de Paiva e Silva Zanta; José Leandro da Silva Duarte (International Journal of Environmental Research, 2023)

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Experimental insecticide applications change tomato pollinator assemblages and do not increase fruit production - Edivani Villaron Franceschinelli; Joicy Martins Morais; Leonardo Lima Bergamini; Igor Madureira de Assis; Luiz Gustavo Fraga Rosa Paniago; Melissa Duarte Tavares Cardoso; Carlos de Melo e Silva Neto; Vanessa Gonzaga Marcelo; Pedro Vale de Azevedo Brito; Luísa Gigante Carvalheiro (Agriculture, Ecosystems & Environment, 2023)

Amazon raw clay as a precursor of a clay-based adsorbent: experimental study and DFT analysis for the adsorption of Basic Yellow 2 dye - Emanuele D. V. Duarte; Wedja T. Vieira; Rodrigo O. Góes; Luiz E. C. de Azevedo; Melissa G. A. Vieira; Meuris G. C. da Silva; Samira M. L. de Carvalho (Environmental Science and Pollution Research, 2023)

Remote sensing for cost-effective blue carbon accounting - Martino E. Malerba; Micheli Duarte de Paula Costa; Daniel A. Friess; Lukas Schuster; Mary A. Young; David Lagomasino; Oscar Serrano; Sharyn M. Hickey; Paul H. York; Michael Rasheed; Jonathan S. Lefcheck; Ben Radford; et al. (Earth-Science Reviews, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Novel infrastructure for coral gardening and reefscaping - Sebastian Schmidt-Roach; Rebecca Klaus; Abdulaziz M. Al-Suwailem; Alejandro R. Prieto; Julian Charrière; Charlotte A. E. Hauser; Carlos M. Duarte; Manuel Aranda (Frontiers in Marine Science, 2023)
Since 1950, coral abundance has declined worldwide by an estimated 60%, and further dramatic declines are predicted. Although global reductions in carbon emissions are essential to prevent further loss, coral reef restoration has become imperative to maintain the ecosystem services that coral reefs provide to humans at local scales. Yet, currently coral restoration and gardening efforts are too expensive to scale up due to the labor-intensive nature of the methods and low success rates. Here, we present a suite of technologies that improve coral reef restoration and rehabilitation’s scalability, efficiency, and effectiveness. Our modular technologies are designed to streamline in and ex situ nursery workflows, reduce maintenance times, solve problems in transporting corals to outplanting sites, and enable rapid outplanting on natural and artificial substrates. These novel structures can act as coral seeding hubs, which placed strategically, can have the capacity to enhance coral reproduction and replenish degraded nearby reefs with larvae. They can be applied to coral restoration and reefscaping, complemented by unique eco-friendly, low-carbon-emission structures for the creation of architecturally and visually appealing habitats and underwater landscapes. Our technologies integrate novel monitoring approaches that support intelligent solutions to track genotypes, optimize and control stock management, apply assisted evolution approaches, and adaptive management through long-term monitoring.

Macrozoobenthos monitoring in Portuguese transitional waters in the scope of the water framework directive using morphology and DNA metabarcoding - Sofia Duarte; Pedro E. Vieira; Barbara R. Leite; Marcos A.L. Teixeira; João M. Neto; Filipe O. Costa (Estuarine, Coastal and Shelf Science, 2023)

FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Vanessa de Fátima Borges; Leticia Selinger Galant; Alexandre Kanashiro; Fernanda Vargas e Silva Castanheira; Valter Vinícius Silva Monteiro; Diego Ângelo Duarte; Filipe Camargo Rodrigues; Camila Meirelles de Souza Silva; Ayda Henriques Schneider; Guilherme Cesar Martelossi Cebinelli; Mikhael Haruo Fernandes de Lima; João Paulo de Biaso Viola; et al. (Inflammation Research, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Adding knowledge to the design of safer hydrophobically modified poly(acrylic) acids: an ecotoxicological approach - Jorge Tavares; Cátia Venâncio; Cláudia Duarte; Filipe E. Antunes; Isabel Lopes (Environmental Science and Pollution Research, 2023)

Speciation process on Brazilian continental islands, with the description of a new insular lancehead of the genus Bothrops (Serpentes, Viperidae) - Fausto E. Barbo; William W. Booker; Marcelo R. Duarte; Betina Chaluppe; José A. Portes-Junior; Francisco L. Franco; Felipe G. Grazziotin (Systematics and Biodiversity, 2022)

The source, level, and balance of nitrogen during the somatic embryogenesis process drive cellular differentiation - Fátima Duarte-Aké; Ruth E. Márquez-López; Zurisadai Monroy-González; Verónica Borbolla-Pérez; Víctor M. Loyola-Vargas (Planta, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

First report of Brenneria goodwinii causing acute oak decline on Quercus suber in Portugal - C. Fernandes; L. Duarte; P. Naves; E. Sousa; L. Cruz (Journal of Plant Pathology, 2022)

Evaluation of air temperature estimated by ERA5-Land reanalysis using surface data in Pernambuco, Brazil - Caio Sérgio Pereira de Araújo; Ivis Andrei Campos e Silva; Matteo Ippolito; Ceres Duarte Guedes Cabral de Almeida (Environmental Monitoring and Assessment, 2022)

Trade-offs between succulent and non-succulent epiphytes underlie variation in drought tolerance and avoidance - S. G. Gotsch; C. B. Williams; R. Bicaba; R. Cruz-de Hoyos; A. Darby; K. Davidson; M. Dix; V. Duarte; A. Glunk; L. Green; B. Ferguson; K. Muñoz-Elizondo; et al. (Oecologia, 2022)

Biodiversity Assessment and Geographical Affinities of Discards in Clam Fisheries in the Atlantic–Mediterranean Transition (Northern Alboran Sea) - J. Urra; P. Marina; A. Rojas García; E. León Duarte; H. Gallardo-Roldán; B. Orue Montaner; M. Lozano; J. M. Serna; A. Garrido; A. J. Ibáñez Yuste; A. Terrón-Sigler; J. Baro; et al. (Thalassas: An International Journal of Marine Sciences, 2021)

Gabra2 is a genetic modifier of Dravet syndrome in mice - Nicole A. Hawkins; Toshihiro Nomura; Samantha Duarte; Levi Barse; Robert W. Williams; Gregg E. Homanics; Megan K. Mulligan; Anis Contractor; Jennifer A. Kearney (Mammalian Genome, 2021)
Pathogenic variants in epilepsy genes result in a spectrum of clinical severity. One source of phenotypic heterogeneity is modifier genes that affect expressivity of a primary pathogenic variant. Mouse epilepsy models also display varying degrees of clinical severity on different genetic backgrounds. Mice with heterozygous deletion of Scn1a ( Scn1a +/− ) model Dravet syndrome, a severe epilepsy most often caused by SCN1A haploinsufficiency. Scn1a +/− mice recapitulate features of Dravet syndrome, including spontaneous seizures, sudden death, and cognitive/behavioral deficits. Scn1a +/− mice maintained on the 129S6/SvEvTac (129) strain have normal lifespan and no spontaneous seizures. In contrast, admixture with C57BL/6J (B6) results in epilepsy and premature lethality. We previously mapped Dravet Survival Modifier loci ( Dsm1-Dsm5 ) responsible for strain-dependent differences in survival. Gabra2 , encoding the GABA A α2 subunit, was nominated as a candidate modifier at Dsm1 . Direct measurement of GABA A receptors found lower abundance of α2-containing receptors in hippocampal synapses of B6 mice relative to 129. We also identified a B6-specific single nucleotide deletion within Gabra2 that lowers mRNA and protein by nearly 50%. Repair of this deletion reestablished normal levels of Gabra2 expression . In this study, we used B6 mice with a repaired Gabra2 allele to evaluate Gabra2 as a genetic modifier of severity in Scn1a +/− mice. Gabra2 repair restored transcript and protein expression, increased abundance of α2-containing GABA A receptors in hippocampal synapses, and rescued epilepsy phenotypes of Scn1a +/− mice. These findings validate Gabra2 as a genetic modifier of Dravet syndrome, and support enhancing function of α 2 -containing GABA A receptors as treatment strategy for Dravet syndrome.

The network structure of intertidal meiofaunal communities from environmental DNA metabarcoding surveys in Northwest Iberia - Bruno Bellisario; Maria Fais; Sofia Duarte; Pedro E. Vieira; Carlos Canchaya; Filipe O. Costa (Aquatic Sciences, 2021)

The role of renin angiotensin system in the pathophysiology of rheumatoid arthritis - Fernanda Rocha Chaves Moreira; Tiago Almeida de Oliveira; Nádia Eliza Ramos; Maria Augusta Duarte Abreu; Ana Cristina Simões e Silva (Molecular Biology Reports, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Effluent treatment using activated carbon adsorbents: a bibliometric analysis of recent literature - Danilo Henrique da Silva Santos; Juliana Cristina Pereira Lima Paulino; Gleybhson Felipe dos Santos Alves; Leonardo Mendonça Tenório de Magalhães Oliveira; Patrícia de Carvalho Nagliate; José Leandro da Silva Duarte; Lucas Meili; Josealdo Tonholo; Carmem Lucia de Paiva e Silva Zanta (Environmental Science and Pollution Research, 2021)

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Seagrass ( Halophila stipulacea ) invasion enhances carbon sequestration in the Mediterranean Sea - Marlene Wesselmann; Nathan R. Geraldi; Carlos M. Duarte; Jordi Garcia‐Orellana; Rubén Díaz‐Rúa; Ariane Arias‐Ortiz; Iris E. Hendriks; Eugenia T. Apostolaki; Núria Marbà (Global Change Biology, 2021)
The introduction and establishment of exotic species often result in significant changes in recipient communities and their associated ecosystem services. However, usually the magnitude and direction of the changes are difficult to quantify because there is no pre‐introduction data. Specifically, little is known about the effect of marine exotic macrophytes on organic carbon sequestration and storage. Here, we combine dating sediment cores ( 210 Pb) with sediment eDNA fingerprinting to reconstruct the chronology of pre‐ and post‐arrival of the Red Sea seagrass Halophila stipulacea spreading into the Eastern Mediterranean native seagrass meadows. We then compare sediment organic carbon storage and burial rates before and after the arrival of H. stipulacea and between exotic ( H. stipulacea) and native ( C. nodosa and P. oceanica ) meadows since the time of arrival following a Before‐After‐Control‐Impact (BACI) approach. This analysis revealed that H. stipulacea arrived at the areas of study in Limassol (Cyprus) and West Crete (Greece) in the 1930s and 1970s, respectively. Average sediment organic carbon after the arrival of H. stipulacea to the sites increased in the exotic meadows twofold, from 8.4 ± 2.5 g C org m −2 year −1 to 14.7 ± 3.6 g C org m −2 year −1 , and, since then, burial rates in the exotic seagrass meadows were higher than in native ones of Cymodocea nodosa and Posidonia oceanica . Carbon isotopic data indicated a 50% increase of the seagrass contribution to the total sediment C org pool since the arrival of H. stipulacea . Our results demonstrate that the invasion of H. stipulacea may play an important role in maintaining the blue carbon sink capacity in the future warmer Mediterranean Sea, by developing new carbon sinks in bare sediments and colonizing areas previously occupied by the colder thermal affinity P. oceanica .

Baseline Study of Trace Element Concentrations in Sediments of the Intertidal Zone of Amazonian Oceanic Beaches - Jéssica C. E. Vilhena; Ana Amorim; Lourenço Ribeiro; Bernardo Duarte; Maíra Pombo (Frontiers in Marine Science, 2021)
Analyzing the presence and quantifying trace elements is of paramount importance to understand natural environmental processes and monitor the degree of anthropogenic disturbance to mitigate impacts already caused. Here, we aimed to establish a baseline of the trace elements profile and concentrations in sandy sediments of intertidal areas of three Amazonian beaches (Brazil). For each beach, sediments were collected from three different sectors (south, center, and north) and five shoreline distance levels (from the high- to the low-water mark), totalizing 15 samples per beach. The concentration of the different trace elements (Mg, Al, P, S, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Br, Rb, Sr, Y, Zr, Cd, Sn, I, Hg, and Pb) was determined by Total reflection X-ray Fluorescence spectrometry. Sediment was also characterized for its grain size, organic matter, and pH. To assess possible enrichment due to anthropogenic activities we compared trace element levels with the values for the Earth’s crust and calculated pollution indexes: geoaccumulation index (Igeo), ecological risk index (RI), contamination factor (CF), pollution load index (PLI), and sediment quality guideline (SQG), threshold effects level (TEL) and probable effects level (PEL). Individual trace metal concentrations did not vary significantly between beaches, sectors, or sample levels, evidencing a homogeneity of trace elements composition and concentrations across this environment. Igeo indicated 62.2% of the sampling stations uncontaminated, 20.0% from uncontaminated to moderately contaminated, and 4.44% (two sampling stations) strongly contaminated, the same two areas classified as high ecological risk by RI. Most of the sampling points presented low CF. Cadmium and Hg were the only elements that showed moderate to very high values of CF. According to the SQGs, 77.7 and 8.8% of the sampling points presented values above the moderate threshold effect level (SQG-TEL) and probable effect level (SQG-PEL), respectively. All points were classified as non-polluted according to the PLI. Our results show that the three beaches present safe levels of almost of the elements demonstrating the good state of preservation. Most of the indexes classified the sampling points as non-polluted, except for Cd and Hg in a few specific sampling points.

Climate‐driven impacts of exotic species on marine ecosystems - Scott Bennett; Julia Santana‐Garcon; Núria Marbà; Gabriel Jorda; Andrea Anton; Eugenia T. Apostolaki; Just Cebrian; Nathan R. Geraldi; Dorte Krause‐Jensen; Catherine E. Lovelock; Paulina Martinetto; John M. Pandolfi; et al. (Global Ecology and Biogeography, 2021)
Aim Temperature is fundamental to the physiological and ecological performance of marine organisms, but its role in modulating the magnitude of ecological impacts by exotic species remains unresolved. Here, we examine the relationship between thermal regimes in the range of origin of marine exotic species and sites of measured impact, after human‐induced introduction. We compare this relationship with the magnitude of impact exerted by exotic species on native ecosystems. Location Global. Time period 1977–2017 (meta‐analysis). Major taxa studied Marine exotic species. Methods Quantitative impacts of exotic species in marine ecosystems were obtained from a global database. The native range of origin of exotic species was used to estimate the realized thermal niche for each species and compared with the latitude and climatic conditions in recipient sites of recorded impact of exotic species. The difference in median temperatures between recipient sites and the thermal range of origin (i.e., thermal midpoint anomaly) was compared with the magnitude of effect sizes by exotic species on native species, communities and ecosystems. Results Recorded impacts occurred predominantly within the thermal niche of origin of exotic species, albeit with a tendency toward higher latitudes and slightly cooler conditions. The severity of impacts by exotic species on abundance of native taxa displayed a hump‐shaped relationship with temperature. Peak impacts were recorded in recipient sites that were 2.2°C cooler than the thermal midpoint of the range of origin of exotic species, and impacts decreased in magnitude toward higher and lower thermal anomalies. Main conclusions Our findings highlight how temperature and climatic context influence ecological impacts by exotic species in marine ecosystems and the implications for existing and novel species interactions under climate change.

The Choroid Plexus Is an Alternative Source of Prolactin to the Rat Brain - Ana R. Costa-Brito; Telma Quintela; Isabel Gonçalves; Ana C. Duarte; Ana R. Costa; Fernando A. Arosa; José E. Cavaco; Manuel C. Lemos; Cecília R. A. Santos (Molecular Neurobiology, 2021)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Spatial distribution of pesticides, organochlorine compounds, PBDEs, and metals in surface marine sediments from Cartagena Bay, Colombia - Edisson Duarte-Restrepo; Katia Noguera-Oviedo; Deena Butryn; Joshua S. Wallace; Diana S. Aga; Beatriz E. Jaramillo-Colorado (Environmental Science and Pollution Research, 2021)

Water assessment of the Itapemirim River/Espírito Santo (Brazil): abiotic and toxicogenetic aspects - Iasmini Nicoli Galter; Ian Drumond Duarte; Maressa Malini; Francielen Barroso Aragão; Ian de Oliveira Martins; Lívia Dorch Rocha; Maria Tereza Weitzel Dias Carneiro; Kamila Soares do Espírito Santo; José Augusto de Oliveira David; e Silvia Tamie Matsumoto (Environmental Science and Pollution Research, 2021)

Diversity of tomato-infecting begomoviruses and spatiotemporal dynamics of an endemic viral species of the Brazilian Atlantic rain forest biome - Macária F. Duarte; Maria E. N. Fonseca; Hélcio Costa; Niday A. N. Fernandes; Ailton Reis; Leonardo S. Boiteux; Rita C. Pereira-Carvalho (Virus Genes, 2021)

Investing in Blue Natural Capital to Secure a Future for the Red Sea Ecosystems - Maha J. Cziesielski; Carlos M. Duarte; Nojood Aalismail; Yousef Al-Hafedh; Andrea Anton; Faiyah Baalkhuyur; Andrew C. Baker; Thorsten Balke; Iliana B. Baums; Michael Berumen; Vasiliki I. Chalastani; Brendan Cornwell; et al. (Frontiers in Marine Science, 2021)
For millennia, coastal and marine ecosystems have adapted and flourished in the Red Sea’s unique environment. Surrounded by deserts on all sides, the Red Sea is subjected to high dust inputs and receives very little freshwater input, and so harbors a high salinity. Coral reefs, seagrass meadows, and mangroves flourish in this environment and provide socio-economic and environmental benefits to the bordering coastlines and countries. Interestingly, while coral reef ecosystems are currently experiencing rapid decline on a global scale, those in the Red Sea appear to be in relatively better shape. That said, they are certainly not immune to the stressors that cause degradation, such as increasing ocean temperature, acidification and pollution. In many regions, ecosystems are already severely deteriorating and are further threatened by increasing population pressure and large coastal development projects. Degradation of these marine habitats will lead to environmental costs, as well as significant economic losses. Therefore, it will result in a missed opportunity for the bordering countries to develop a sustainable blue economy and integrate innovative nature-based solutions. Recognizing that securing the Red Sea ecosystems’ future must occur in synergy with continued social and economic growth, we developed an action plan for the conservation, restoration, and growth of marine environments of the Red Sea. We then investigated the level of resources for financial and economic investment that may incentivize these activities. This study presents a set of commercially viable financial investment strategies, ecological innovations, and sustainable development opportunities, which can, if implemented strategically, help ensure long-term economic benefits while promoting environmental conservation. We make a case for investing in blue natural capital and propose a strategic development model that relies on maintaining the health of natural ecosystems to safeguard the Red Sea’s sustainable development.

Losses of Soil Organic Carbon with Deforestation in Mangroves of Madagascar - Ariane Arias-Ortiz; Pere Masqué; Leah Glass; Lisa Benson; Hilary Kennedy; Carlos M. Duarte; Jordi Garcia-Orellana; Claudia R. Benitez-Nelson; Marc S. Humphries; Ismaël Ratefinjanahary; Jaona Ravelonjatovo; Catherine E. Lovelock (Ecosystems, 2021)

Effects of thermal shock on the survival and reproduction of Stratiolaelaps scimitus (Mesostigmata: Laelapidae) - Priscilla C. Gobbi; Juliano L. P. Duarte; Lucas R. da Silva; Dori E. Nava; Gustavo Sessa Fialho; Uemerson S. da Cunha; Adriane da F. Duarte (Experimental and Applied Acarology, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Undecane production by cold-adapted bacteria from Antarctica - Michel Rodrigo Zambrano Passarini; Tiago Rodrigues e Silva; Suzan Prado Fernandes Bernal; Nathália Luana Cecchet; Adilson Sartoratto; Marcela Boroski; Alysson Wagner Fernandes Duarte; Júlia Ronzella Ottoni; Luiz Henrique Rosa; Valéria Maia de Oliveira (Extremophiles, 2020)

Costus stripe mosaic virus, a tentative new member of the genus Potyvirus - M. Amelia V. Alexandre; Ligia M. L. Duarte; Pedro L. Ramos-González; Alexandre L. R. Chaves; Ricardo Harakava; Leilane K. Rodrigues; Camila Chabi-Jesus; E. W. Kitajima (Archives of Virology, 2020)

The Impact of Science-Unbased Measures Against COVID-19 in Clinical Decision-Making Process - João Vitor Cândido Pimentel; Thaíse Duarte Onofre Sabiá e Silva; Ana Beatriz Tavares Filgueiras; Modesto Leite Rolim Neto (AAPS PharmSciTech, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Beyond Reef Restoration: Next-Generation Techniques for Coral Gardening, Landscaping, and Outreach - Sebastian Schmidt-Roach; Carlos M. Duarte; Charlotte A. E. Hauser; Manuel Aranda (Frontiers in Marine Science, 2020)

Nicorandil Affects Mitochondrial Respiratory Chain Function by Increasing Complex III Activity and ROS Production in Skeletal Muscle Mitochondria - E. Sánchez-Duarte; C. Cortés-Rojo; L. A. Sánchez-Briones; J. Campos-García; A. Saavedra-Molina; I. Delgado-Enciso; U. A. López-Lemus; R. Montoya-Pérez (The Journal of Membrane Biology, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

The big picture of field hydrology studies in Brazil - Davi C. D. Melo; Jamil A. A. Anache; Cristiano das N. Almeida; Jaqueline V. Coutinho; Geraldo M. Ramos Filho; Lívia M. P. Rosalem; Natália S. Pelinson; Guilherme L. R. A. Ferreira; Dimaghi Schwamback; Kalyl G. Calixto; João P. G. Siqueira; Jean C. Duarte-Carvajalino; et al. (Hydrological Sciences Journal, 2020)

Estimating the Potential Blue Carbon Gains From Tidal Marsh Rehabilitation: A Case Study From South Eastern Australia - Anne Gulliver; Paul E. Carnell; Stacey M. Trevathan-Tackett; Micheli Duarte de Paula Costa; Pere Masqué; Peter I. Macreadie (Frontiers in Marine Science, 2020)

Degradation of a Sunset Yellow and Tartrazine Dye Mixture: Optimization Using Statistical Design and Empirical Mathematical Modeling - G. E. do Nascimento; V. O. M. Cavalcanti; R. M. R. Santana; D. C. S. Sales; J. M. Rodríguez-Díaz; D. C. Napoleão; M. M. M. B. Duarte (Water, Air, & Soil Pollution, 2020)

Evaluation of a cattle rapid test for early pregnancy diagnosis in sheep - Camila de Miranda e Silva Chaves; Ricardo Lopes Dias da Costa; Keila Maria Roncato Duarte; Renato Travassos Beltrame; Celia Raquel Quirino (Tropical Animal Health and Production, 2020)

Non-Cytotoxic Sulfated Heterorhamnan from Gayralia brasiliensis Green Seaweed Reduces Driver Features of Melanoma Metastatic Progression - D. L. Bellan; E. Mazepa; S. M. P. Biscaia; J. P. Gonçalves; C. C. Oliveira; G. R. Rossi; L. G. Ferreira; M. D. Noseda; E. S. Trindade; M. E. R. Duarte; C. R. C. Franco (Marine Biotechnology, 2020)

Reconciling Tourism Development and Conservation Outcomes Through Marine Spatial Planning for a Saudi Giga-Project in the Red Sea (The Red Sea Project, Vision 2030) - Vasiliki I. Chalastani; Panos Manetos; Abdulaziz M. Al-Suwailem; Jason A. Hale; Abhishekh P. Vijayan; John Pagano; Ian Williamson; Scott D. Henshaw; Raed Albaseet; Faisal Butt; Russell E. Brainard; Harry Coccossis; et al. (Frontiers in Marine Science, 2020)

Concomitant taurine exposure counteracts ethanol-induced changes in locomotor and anxiety-like responses in zebrafish - Barbara D. Fontana; Tamie Duarte; Talise E. Müller; Julia Canzian; Paola R. Ziani; Nathana J. Mezzomo; Matthew O. Parker; Denis B. Rosemberg (Psychopharmacology, 2020)
Taurine (TAU) is a β-amino sulfonic acid with pleiotropic roles in the brain, including the neuromodulatory activity via GABAergic and glycinergic agonism. This molecule is found at high concentrations in energy drinks and is often mixed with alcohol in beverages. Although TAU has a neuroprotective role in the brain, the putative risks of mixing TAU and EtOH are not fully understood. Here, we investigated whether TAU modulates locomotor and anxiety-like behavior in adult zebrafish by using the novel tank and light-dark tests following acute EtOH exposure at anxiogenic and anxiolytic concentrations. Zebrafish were individually exposed to water (control), TAU (42, 150, and 400 mg/L), and EtOH (0.25% (v/v) and 1% (v/v)) both independently and cotreated for 1 h. EtOH 0.25% and TAU produced U-shape anxiolytic-like behavior in the light-dark test, TAU 42 and 400 positively modulated EtOH effects, and TAU 150 exerted a protective effect. All TAU concentrations counteracted EtOH 1%-induced locomotion impairment, as well as the anxiogenic-like behavior. Finally, all TAU concentrations when given independently or cotreated with EtOH 0.25% and 1% decreased the risk assessment of the lit compartment. Principal component analyses revealed that exploration and anxiety-like responses were the main behaviors that contribute to the effects of TAU and EtOH. Overall, we demonstrate that TAU differently modulates EtOH-induced anxiolytic- and anxiogenic-like behaviors depending on the concentration, suggesting a complex mechanism underlying TAU and EtOH interactions.

Ecological effects of non‐native species in marine ecosystems relate to co‐occurring anthropogenic pressures - Nathan R. Geraldi; Andrea Anton; Julia Santana‐Garcon; Scott Bennett; Nuria Marbà; Catherine E. Lovelock; Eugenia T. Apostolaki; Just Cebrian; Dorte Krause‐Jensen; Paulina Martinetto; John M. Pandolfi; Carlos M. Duarte (Global Change Biology, 2020)
Predictors for the ecological effects of non‐native species are lacking, even though such knowledge is fundamental to manage non‐native species and mitigate their impacts. Current theories suggest that the ecological effects of non‐native species may be related to other concomitant anthropogenic stressors, but this has not been tested at a global scale. We combine an exhaustive meta‐analysis of the ecological effects of marine non‐native species with human footprint proxies to determine whether the ecological changes due to non‐native species are modulated by co‐occurring anthropogenic impacts. We found that non‐native species had greater negative effects on native biodiversity where human population was high and caused reductions in individual performance where cumulative human impacts were large. On this basis we identified several marine ecoregions where non‐native species may have the greatest ecological effects, including areas in the Mediterranean Sea and along the northwest coast of the United States. In conclusion, our global assessment suggests coexisting anthropogenic impacts can intensify the ecological effects of non‐native species.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of leaf extracts of Protium spruceanum against adult and larval Rhipicephalus microplus - J. C. G. Figueiredo; Y. R. F. Nunes; Viviane de Oliveira Vasconcelos; S. R. Arruda; F. Morais-Costa; G. S. C. Santos; F. S. Alvez; E. R. Duarte (Experimental and Applied Acarology, 2019)

Trophic ecology of benthic fish assemblages in a lowland river in the Brazilian Amazon - Cleber Duarte; Anne E. Magurran; Jansen Zuanon; Cláudia P. Deus (Aquatic Ecology, 2019)

Peeling the Otolith of Fish: Optimal Parameterization for Micro-CT Scanning - Jonas E. Vasconcelos-Filho; Felix S. L. Thomsen; Borko Stosic; Antonio C. D. Antonino; Daniel A. Duarte; Richard J. Heck; Rosangela P. T. Lessa; Francisco M. Santana; Beatrice P. Ferreira; Paulo J. Duarte-Neto (Frontiers in Marine Science, 2019)

Collaborative Database to Track Mass Mortality Events in the Mediterranean Sea - Joaquim Garrabou; Daniel Gómez-Gras; Jean-Baptiste Ledoux; Cristina Linares; Nathaniel Bensoussan; Paula López-Sendino; Hocein Bazairi; Free Espinosa; Mohamed Ramdani; Samir Grimes; Mouloud Benabdi; Jamila Ben Souissi; et al. (Frontiers in Marine Science, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Tactile Stimulation on Adulthood Modifies the HPA Axis, Neurotrophic Factors, and GFAP Signaling Reverting Depression-Like Behavior in Female Rats - Kr. Roversi; Caren Tatiane de David Antoniazzi; L. H. Milanesi; H. Z. Rosa; M. Kronbauer; D. R. Rossato; T. Duarte; M. M. Duarte; Marilise E. Burger (Molecular Neurobiology, 2019)

Tomato mottle mosaic virus in Brazil and its relationship with Tm-22 gene - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Lázaro E. P. Peres; Déborah Y. A. C. dos Santos (European Journal of Plant Pathology, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Carbon and Nitrogen Concentrations, Stocks, and Isotopic Compositions in Red Sea Seagrass and Mangrove Sediments - Neus Garcias-Bonet; Antonio Delgado-Huertas; Paloma Carrillo-de-Albornoz; Andrea Anton; Hanan Almahasheer; Núria Marbà; Iris E. Hendriks; Dorte Krause-Jensen; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Fingerprinting Blue Carbon: Rationale and Tools to Determine the Source of Organic Carbon in Marine Depositional Environments - Nathan R. Geraldi; Alejandra Ortega; Oscar Serrano; Peter I. Macreadie; Catherine E. Lovelock; Dorte Krause-Jensen; Hilary Kennedy; Paul S. Lavery; Michael L. Pace; Joeri Kaal; Carlos M. Duarte (Frontiers in Marine Science, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

A standard area diagram set for severity assessment of botrytis leaf blight of onion - Edivânio R. Araújo; Renata S. Resende; Carlos E. Krezanoski; Henrique S. S. Duarte (European Journal of Plant Pathology, 2019)

Surface impurities on giant gypsum crystals from “la Cueva de las Espadas” (Cave of Swords), Naica, Mexico - Isaí Castillo-Sandoval; Luis E. Fuentes-Cobas; Bernardo E. Pérez-Cazares; Hilda E. Esparza-Ponce; María E. Fuentes-Montero; Hiram Castillo-Michel; Diane Eichert; Ignacio Reyes-Cortes; Iván J. Carreño-Márquez; José M. Napoles-Duarte; María E. Montero-Cabrera (Mineralogy and Petrology, 2018)

Investigating taxon boundaries and extinction risk in endemic Chilean cacti (Copiapoa subsection Cinerei, Cactaceae) using chloroplast DNA sequences, microsatellite data and 3D mapping - Isabel Larridon; Emily Veltjen; Ilias Semmouri; Pieter Asselman; Pablo C. Guerrero; Milén Duarte; Helmut E. Walter; Mauricio A. Cisternas; Marie-Stéphanie Samain (Kew Bulletin, 2018)

Impact of incorporating ABCB1 and CYP4F2 polymorphisms in a pharmacogenetics-guided warfarin dosing algorithm for the Brazilian population - Letícia C. Tavares; Nubia E. Duarte; Leiliane R. Marcatto; Renata A. G. Soares; Jose E. Krieger; Alexandre C. Pereira; Paulo Caleb Junior Lima Santos (European Journal of Clinical Pharmacology, 2018)

Scirtothrips dorsalis (Thysanoptera: Thripidae): a Newly Introduced Polyphagous Pest in Northeastern Brazil - N S Dias-Pini; M G A Lima; E F B Lima; G P S Maciel; P M Duarte (Neotropical Entomology, 2018)

Stable Isotope (δ13C, δ15N, δ18O, δD) Composition and Nutrient Concentration of Red Sea Primary Producers - Carlos M. Duarte; Antonio Delgado-Huertas; Andrea Anton; Paloma Carrillo-de-Albornoz; Daffne C. López-Sandoval; Susana Agustí; Hanan Almahasheer; Núria Marbá; Iris E. Hendriks; Dorte Krause-Jensen; Neus Garcias-Bonet (Frontiers in Marine Science, 2018)

Combination Therapy with Sulfasalazine and Valproic Acid Promotes Human Glioblastoma Cell Death Through Imbalance of the Intracellular Oxidative Response - Carlos Gustavo Garcia; Suzana Assad Kahn; Luiz Henrique Medeiros Geraldo; Igor Romano; Ivan Domith; Deborah Christinne Lima e Silva; Fernando dos Santos Assunção; Marcos José Ferreira; Camila Cabral Portugal; Jorge Marcondes de Souza; Luciana Ferreira Romão; Annibal Duarte Pereira Netto; et al. (Molecular Neurobiology, 2018)

The occurrence of wild cotton Gossypium mustelinum Miers ex Watt populations in the coast of Pernambuco, Northeastern Brazil - Edson Ferreira da Silva; Luiz Sergio Costa Duarte Filho; Ana Kelly dos Santos Maia; Allison Vieira da Silva; Ana Carolina Borges Lins e Silva (Genetic Resources and Crop Evolution, 2018)

Efficacy of plants extracts from the Cerrado against adult female of Dermacentor nitens (Acari: Ixodidae) - V. O. Vasconcelos; E. G. L. Costa; V. R. Moreira; F. Morais-Costa; E. R. Duarte (Experimental and Applied Acarology, 2018)

Microwave-assisted synthesis of borneol esters and their antimicrobial activity - Aline Teixeira Maciel e Silva; Vinícius Viana Pereira; Jacqueline Aparecida Takahashi; Roqueline Rodrigues Silva; Lucienir Pains Duarte (Natural Product Research, 2018)

Aged rats are more vulnerable than adolescents to “ecstasy”-induced toxicity - R. Feio-Azevedo; V. M. Costa; D. J. Barbosa; A. Teixeira-Gomes; I. Pita; S. Gomes; F. C. Pereira; M. Duarte-Araújo; J. A. Duarte; F. Marques; E. Fernandes; M. L. Bastos; et al. (Archives of Toxicology, 2018)

Effects of a nanoemulsion with Copaifera officinalis oleoresin against monogenean parasites of Colossoma macropomum: A Neotropical Serrasalmidae - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; C Solans; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Monogeneans are ectoparasites that may cause losses in production and productivity in the aquaculture of Colossoma macropomum . Chemotherapeutics used in aquaculture usually have major adverse effects on fish; hence, the use of essential oils has been considered advantageous, but these are not soluble in water. Thus, the use of nanostructures to enhance water solubility of compounds and improve bioactivity may be very promising. This study investigated the antiparasitic activity of nanoemulsion prepared with Copaifera officinalis oleoresin (50, 100, 150, 200 and 300 mg/L), against monogenean parasites from the gills of C. macropomum . The particle size distribution and zeta potential suggested that a potentially kinetic stable system was generated. The nanoemulsion from C. officinalis oleoresin achieved high efficacy (100%) at low concentrations (200 and 300 mg/L) after 15 min of exposure. This was the first time that a nanoemulsion was generated from C. officinalis oleoresin using a solvent‐free, non‐heating and low‐energy method. Moreover, this was the first time that an antiparasitic against monogeneans on fish gills, based on nanoemulsion of C. officinalis oleoresin, was tested.

Oxidative stress in the hydrocoral Millepora alcicornis exposed to CO2-driven seawater acidification - Débora Camacho Luz; Yuri Dornelles Zebral; Roberta Daniele Klein; Joseane Aparecida Marques; Laura Fernandes de Barros Marangoni; Cristiano Macedo Pereira; Gustavo Adolpho Santos Duarte; Débora de Oliveira Pires; Clovis Barreira e Castro; Emiliano Nicolas Calderon; Adalto Bianchini (Coral Reefs, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

β-(1→6)-d-glucan secreted during the optimised production of exopolysaccharides by Paecilomyces variotii has immunostimulatory activity - Erica F. Osaku; Rafael A. Menolli; Claudia R. L. de M. Costa; Fernando Henrique G. Tessaro; Renan H. de Melo; Alex E. do Amaral; Péricles A. D. Duarte; Arquimedes Paixão de Santana Filho; Andrea Caroline Ruthes; José Luis da C. Silva; Rosiane G. Mello (Antonie van Leeuwenhoek, 2018)

Iron Deficiency in Seagrasses and Macroalgae in the Red Sea Is Unrelated to Latitude and Physiological Performance - Andrea Anton; Iris E. Hendriks; Núria Marbà; Dorte Krause-Jensen; Neus Garcias-Bonet; Carlos M. Duarte (Frontiers in Marine Science, 2018)

Nanoemulsion from essential oil of Pterodon emarginatus (Fabaceae) shows in vitro efficacy against monogeneans of Colossoma macropomum (Pisces: Serrasalmidae) - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; E C Conceição; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Outbreaks of diseases pose a major threat to sustainable aquaculture development worldwide. Application of herbal products to combat parasitic diseases provides an alternative approach for sustainable aquaculture. This study investigated the in vitro antiparasitic effects of an oil‐in‐water nanoemulsion prepared using the essential oil from Pterodon emarginatus , against monogeneans infesting Colossoma macropomum . Gill arches from C. macropomum (47.6 ± 14.5 g and 13.5 ± 1.4 cm) that were naturally parasitized by Anacanthorus spathulatus , Notozothecium janauachensis and Mymarothecium boegeri were immersed in different dispersions of the P. emarginatus nanoemulsions (0, 50, 100, 200, 400 and 600 mg/L). The major compounds presented in the essential oil of P. emarginatus were β‐elemene, β‐caryophyllene and α‐humulene. Characterization of these nanoemulsions showed that they have a small mean droplet size and low polydispersity index, which is concordant with stable systems. In this in vitro trial, the P. emarginatus nanoemulsion concentrations of 100, 200, 400 and 600 mg/L presented 100% helminthic efficacy against monogeneans of the gills of C. macropomum . The highest two concentrations used (400 and 600 mg/L) were seen to immobilize the parasites after only 15 min. Therefore, it would be worthwhile testing these concentrations in therapeutic baths against monogeneans of C. macropomum .

Relevance of genetic relationship in GWAS and genomic prediction - Helcio Duarte Pereira; José Marcelo Soriano Viana; Andréa Carla Bastos Andrade; Fabyano Fonseca e Silva; Geísa Pinheiro Paes (Journal of Applied Genetics, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Correction to: pH gradients in the diffusive boundary layer of subarctic macrophytes - Iris E. Hendriks; Carlos M. Duarte; Núria Marbà; Dorte Krause-Jensen (Polar Biology, 2017)

pH gradients in the diffusive boundary layer of subarctic macrophytes - Iris E. Hendriks; Carlos M. Duarte; Núria Marbà; Dorte Krause-Jensen (Polar Biology, 2017)

Cell Penetration and Secondary Structure of a Synthetic Peptide with Anti-HIV Activity - Taimi E. Paneque; Anna C. Ramírez-Suárez; Dionne Casillas; Carlos A. Duarte; Glay Chinea; Carlos Espinosa-Viñals; Hilda Garay; Llilian Gómez-Pérez; Celia Fernández-Ortega (International Journal of Peptide Research and Therapeutics, 2017)

Effects of CO2-driven acidification of seawater on the calcification process in the calcareous hydrozoan Millepora alcicornis (Linnaeus, 1758) - Laura Fernandes de Barros Marangoni; Emiliano Nicolas Calderon; Joseane Aparecida Marques; Gustavo Adolpho Santos Duarte; Cristiano Macedo Pereira; Clovis Barreira e Castro; Adalto Bianchini (Coral Reefs, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Middle-Aged Diabetic Females and Males Present Distinct Susceptibility to Alzheimer Disease-like Pathology - E. Candeias; A. I. Duarte; I. Sebastião; M. A. Fernandes; A. I. Plácido; C. Carvalho; S. Correia; R. X. Santos; R. Seiça; M. S. Santos; C. R. Oliveira; P. I. Moreira (Molecular Neurobiology, 2017)

Cognitive Event-Related Potentials (P300) and Cognitive Impairment in Duchenne Muscular Dystrophy - N. Esquitin-Garduño; R. E. Escobar-Cedillo; B. G. Flores-Avalos; G. Escobar-Cedillo; A. Miranda-Duarte; L. B. López-Hernández; V. I. Orellana-Villazón; R. M. Coral-Vázquez; S. García; B. Gómez-Díaz (Neurophysiology, 2017)

Is Climate Change Shifting the Poleward Limit of Mangroves? - Sharyn M. Hickey; Stuart R. Phinn; Nik J. Callow; Kimberly P. Van Niel; Jeff E. Hansen; Carlos M. Duarte (Estuaries and Coasts, 2017)

Guanosine Exerts Neuroprotective Effect in an Experimental Model of Acute Ammonia Intoxication - G. F. Cittolin-Santos; A. M. de Assis; P. A. Guazzelli; L. G. Paniz; J. S. da Silva; M. E. Calcagnotto; G. Hansel; K. C. Zenki; E. Kalinine; M. M. Duarte; D. O. Souza (Molecular Neurobiology, 2017)

Improvements in precipitation simulation over South America for past and future climates via multi-model combination - Maytê Duarte Leal Coutinho; Kellen Carla Lima; Cláudio Moisés Santos e Silva (Climate Dynamics, 2017)

Serious fungal infections in Chile - E. Alvarez Duarte; D. W. Denning (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Autochthonous and allochthonous contributions of organic carbon to microbial food webs in Svalbard fjords - Johnna M. Holding; Carlos M. Duarte; Antonio Delgado‐Huertas; Karline Soetaert; Jorien E. Vonk; Susana Agustí; Paul Wassmann; Jack J. Middelburg (Limnology and Oceanography, 2017)
Rising temperatures in the Arctic Ocean are causing sea ice and glaciers to melt at record breaking rates, which has consequences for carbon cycling in the Arctic Ocean that are yet to be fully understood. Microbial carbon cycling is driven by internal processing of in situ produced organic carbon (OC), however recent research suggests that melt water from sea ice and glaciers could introduce an allochthonous source of OC to the microbial food web with ramifications for the metabolic balance of plankton communities. In this study, we characterized autochthonous and allochthonous sources of OC to the Western Svalbard fjord system using stable isotopes of carbon. We quantified δ 13 C of eukaryotic and prokaryotic planktonic groups using polar lipid‐derived fatty acids as biomarkers in addition to measuring δ 13 C of marine particulate OC and dissolved OC from glacial runoff. δ 13 C of bacteria (−22.5‰) was higher than that of glacial runoff OC (−28.5‰) and other phytoplankton groups (−24.7 to −29.1‰), which suggests that marine bacteria preferentially use a third source of OC. We present a Bayesian three‐source δ 13 C mixing model whereby ∼ 60% of bacteria carbon is derived from OC in sea ice, and the remaining carbon is derived from autochthonous production and glacial‐derived OC. These results suggest that subsidies of OC from melting glaciers will not likely influence microbial carbon cycling in Svalbard fjords in the future and that further research is needed to determine the effects of melting sea ice on microbial carbon cycling in fjord systems and elsewhere in the Arctic Ocean.

Entangled fates of holobiont genomes during invasion: nested bacterial and host diversities in Caulerpa taxifolia - S. Arnaud‐Haond; T. Aires; R. Candeias; S. J. L. Teixeira; C. M. Duarte; M. Valero; E. A. Serrão (Molecular Ecology, 2017)
Successful prevention and mitigation of biological invasions requires retracing the initial steps of introduction, as well as understanding key elements enhancing the adaptability of invasive species. We studied the genetic diversity of the green alga Caulerpa taxifolia and its associated bacterial communities in several areas around the world. The striking congruence of α and β diversity of the algal genome and endophytic communities reveals a tight association, supporting the holobiont concept as best describing the unit of spreading and invasion. Both genomic compartments support the hypotheses of a unique accidental introduction in the Mediterranean and of multiple invasion events in southern Australia. In addition to helping with tracing the origin of invasion, bacterial communities exhibit metabolic functions that can potentially enhance adaptability and competitiveness of the consortium they form with their host. We thus hypothesize that low genetic diversities of both host and symbiont communities may contribute to the recent regression in the Mediterranean, in contrast with the persistence of highly diverse assemblages in southern Australia. This study supports the importance of scaling up from the host to the holobiont for a comprehensive understanding of invasions.

Weight, body condition, milk production, and metabolism of Nellore cows when their calves are submitted to different supplementation levels - Aline Gomes da Silva; Mário Fonseca Paulino; Lincoln da Silva Amorim; Edenio Detmann; Luciana Navajas Rennó; Márcio de Souza Duarte; Felipe Henrique de Moura; Luciano Prímola de Melo; Paulo Henrique Silva e Paiva; Marcos Rocha Manso; Victor Valério de Carvalho (Tropical Animal Health and Production, 2017)

Biological and molecular characterization of a putative new potexvirus infecting Senna occidentalis - Jorge A. M. Rezende; Viviana M. Camelo-García; Sónia C. S. Andrade; José E. Buriolla; Elliot W. Kitajima; Ligia M. L. Duarte (Archives of Virology, 2017)

Cytotoxicity and oxidative stress responses of silica-coated iron oxide nanoparticles in CHSE-214 cells - K. Srikanth; Tito Trindade; A. C. Duarte; E. Pereira (Environmental Science and Pollution Research, 2017)

Home sweet home: evidence for nest‐fidelity in the rocky intertidal fish, the shanny L ipophrys pholis - J. Martins; F. Almada; A. Gonçalves; P. Duarte‐Coelho; P. E. Jorge (Journal of Fish Biology, 2017)
The ability to be faithful to a particular area or site was analysed in the shanny Lipophrys pholis . Using passive integrated transponders, adults from a population of L. pholis at Cabo Raso, Portugal, were followed over a period of 3 years. The findings showed that site fidelity is a consistent behaviour during the breeding season with specific breeding males being found only in particular sectors within the area, and in specific nests throughout the years. The fact that, in general, L. pholis individuals were absent from the study area during the non‐breeding season and breeding males were recorded returning to the same nests and sectors for consecutive breeding seasons suggests that they have developed excellent homing abilities. Translocation data corroborate this idea showing that breeding males successfully returned to their nests after a displacement of >100 m. Altogether, these findings highlight the relevance of life‐history traits ( e.g. nesting) in the conditioning of site fidelity and homing for this species of rocky intertidal fish, and more importantly, provide evidence for the need of a well‐developed navigational system.

Music supported therapy promotes motor plasticity in individuals with chronic stroke - P. Ripollés; N. Rojo; J. Grau-Sánchez; J. L. Amengual; E. Càmara; J. Marco-Pallarés; M. Juncadella; L. Vaquero; F. Rubio; E. Duarte; C. Garrido; E. Altenmüller; et al. (Brain Imaging and Behavior, 2016)

Topography‐driven isolation, speciation and a global increase of endemism with elevation - Manuel J. Steinbauer; Richard Field; John‐Arvid Grytnes; Panayiotis Trigas; Claudine Ah‐Peng; Fabio Attorre; H. John B. Birks; Paulo A. V. Borges; Pedro Cardoso; Chang‐Hung Chou; Michele De Sanctis; Miguel M. de Sequeira; et al. (Global Ecology and Biogeography, 2016)
Aim Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location Thirty‐two insular and 18 continental elevational gradients from around the world. Methods We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic (‘percent endemism’) in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.

Further drimane sesquiterpenes from Drimys brasiliensis stem barks with cytotoxic potential - Eduarda Fratoni; Vanessa Duarte Claudino; Rosendo Augusto Yunes; Gilberto C. Franchi; Alexandre E. Nowill; Valdir Cechinel Filho; Franco Delle Monache; Angela Malheiros (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

Biofortification of wheat, rice and common bean by applying foliar zinc fertilizer along with pesticides in seven countries - H. Ram; A. Rashid; W. Zhang; A. P. Duarte; N. Phattarakul; S. Simunji; M. Kalayci; R. Freitas; B. Rerkasem; R. S. Bal; K. Mahmood; E. Savasli; et al. (Plant and Soil, 2016)

Comparative study on metal biosorption by two macroalgae in saline waters: single and ternary systems - Paula Figueira; Bruno Henriques; Ana Teixeira; Cláudia B. Lopes; Ana T. Reis; Rui J. R. Monteiro; A. C. Duarte; M. A. Pardal; E. Pereira (Environmental Science and Pollution Research, 2016)

The concerted impact of domestication and transposon insertions on methylation patterns between dogs and grey wolves - Ilana Janowitz Koch; Michelle M. Clark; Michael J. Thompson; Kerry A. Deere‐Machemer; Jun Wang; Lionel Duarte; Gitanjali E. Gnanadesikan; Eskender L. McCoy; Liudmilla Rubbi; Daniel R. Stahler; Matteo Pellegrini; Elaine A. Ostrander; et al. (Molecular Ecology, 2016)
The process of domestication can exert intense trait‐targeted selection on genes and regulatory regions. Specifically, rapid shifts in the structure and sequence of genomic regulatory elements could provide an explanation for the extensive, and sometimes extreme, variation in phenotypic traits observed in domesticated species. Here, we explored methylation differences from >24 000 cytosines distributed across the genomes of the domesticated dog ( Canis familiaris ) and the grey wolf ( Canis lupus ). PCA and model‐based cluster analyses identified two primary groups, domestic vs. wild canids. A scan for significantly differentially methylated sites ( DMS s) revealed species‐specific patterns at 68 sites after correcting for cell heterogeneity, with weak yet significant hypermethylation typical of purebred dogs when compared to wolves (59% and 58%, P 66%) of differentially methylated regions contained or were associated with repetitive elements, indicative of a genotype‐mediated trend. However, DMS s were also often linked to functionally relevant genes (e.g. neurotransmitters). Finally, we utilized known genealogical relationships among Yellowstone wolves to survey transmission stability of methylation marks, from which we found a substantial fraction that demonstrated high heritability (both H 2 and h 2 > 0.99). These analyses provide a unique epigenetic insight into the molecular consequences of recent selection and radiation of our most ancient domesticated companion, the dog. These findings suggest selection has acted on methylation patterns, providing a new genomic perspective on phenotypic diversification in domesticated species.

Regional climate simulations of the changes in the components of the moisture budget over South America - Maytê Duarte Leal Coutinho; Kellen Carla Lima; Cláudio Moisés Santos e Silva (International Journal of Climatology, 2016)
The moisture transport over South America ( SA ) was investigated through the vertically integrated moisture flux of three regions: the Amazon ( AMZ ), Northeastern Brazil ( NEB ) and the La Plata Basin ( LPB ), in different climates, past (1961–1990) and future (2071–2100), in the summer ( DJF ) and winter ( JJA ) seasons. For this, we used the results of the simulations of four regional climate models ( RCMs ) of the Regional Climate Change Assessment for the La Plata Basin ( CLARIS‐LPB ) project. The capacity and limitations of the models to simulate seasonal precipitation for the past period is discussed. In general, the RCMs tended to overestimate the observed precipitation during DJF in the NEB and underestimate it during JJA in the LPB . In relation to change in precipitation (future minus past), the RCMs indicated a decrease in precipitation over northern SA . The average fluxes of the AMZ and NEB regions provided most of the water vapour through the east and north edges, which indicates that the contributions of the North and South Atlantic trade winds are equally important for the entry of moisture during JJA and DJF . This configuration was observed in all models and climates. By comparing past and future climates, the moisture flux convergence during the past was lower relative to the future in different regions and seasons, with statistically significant differences at the 5% level considering the Student's t ‐test. In the same study, we compared the simulated ( RCMs ) and reanalysis moisture flux ( ERA ‐40) in the past climate. The result indicated that the CLARIS project's RCMs are capable of simulating values similar or equal to the observed ones, providing high quality data for SA that can be useful in the analysis of changes in future moisture fluxes.

Social immunity of the family: parental contributions to a public good modulated by brood size - Ana Duarte; Sheena C. Cotter; Catherine E. Reavey; Richard J. S. Ward; Ornela De Gasperin; Rebecca M. Kilner (Evolutionary Ecology, 2016)

Juvenile Pen Shells (Pinna nobilis) Tolerate Acidification but Are Vulnerable to Warming - Lorena Basso; Iris E. Hendriks; Carlos M. Duarte (Estuaries and Coasts, 2015)

Extreme pH Conditions at a Natural CO2 Vent System (Italy) Affect Growth, and Survival of Juvenile Pen Shells (Pinna nobilis) - Lorena Basso; Iris E. Hendriks; Alejandro B. Rodríguez-Navarro; Maria C. Gambi; Carlos M. Duarte (Estuaries and Coasts, 2015)

Mites associated with sugarcane crop and with native trees from adjacent Atlantic forest fragment in Brazil - Mércia E. Duarte; Denise Navia; Lucas R. dos Santos; Pedro J. S. Rideiqui; Edmilson S. Silva (Experimental and Applied Acarology, 2015)

Synergistic effects of hypoxia and increasing CO2 on benthic invertebrates of the central Chilean coast - Alexandra Steckbauer; Laura Ramajo; Iris E. Hendriks; Miriam Fernandez; Nelson A. Lagos; Luis Prado; Carlos M. Duarte (Frontiers in Marine Science, 2015)

Size-Dependent Arsenic Accumulation in Scrobicularia plana in a Temperate Coastal Lagoon (Ria de Aveiro, Portugal) - T. Ereira; J. P. Coelho; A. C. Duarte; M. A. Pardal; M. E. Pereira (Water, Air, & Soil Pollution, 2015)

Effects of resistance training on neuromuscular characteristics and pacing during 10-km running time trial - Mayara V. Damasceno; Adriano E. Lima-Silva; Leonardo A. Pasqua; Valmor Tricoli; Marcos Duarte; David J. Bishop; Rômulo Bertuzzi (European Journal of Applied Physiology, 2015)

Nickel and Copper Toxicity to Embryos of the Long-Spined Sea Urchin, Diadema savignyi - G. Rosen; I. Rivera-Duarte; M. A. Colvin; R. E. Dolecal; L. J. Raymundo; P. J. Earley (Bulletin of Environmental Contamination and Toxicology, 2015)

Population genetic structure of Bombus terrestris in Europe: Isolation and genetic differentiation of Irish and British populations - António S. Moreira; Finbarr G. Horgan; Tomás E. Murray; Thomais Kakouli‐Duarte (Molecular Ecology, 2015)
The genetic structure of the earth bumblebee ( Bombus terrestris L.) was examined across 22 wild populations and two commercially reared populations using eight microsatellite loci and two mitochondrial genes. Our study included wild bumblebee samples from six populations in Ireland, one from the Isle of Man, four from Britain and 11 from mainland Europe. A further sample was acquired from New Zealand. Observed levels of genetic variability and heterozygosity were low in Ireland and the Isle of Man, but relatively high in continental Europe and among commercial populations. Estimates of F st revealed significant genetic differentiation among populations. Bayesian cluster analysis indicated that Irish populations were highly differentiated from British and continental populations, the latter two showing higher levels of admixture. The data suggest that the Irish Sea and prevailing south westerly winds act as a considerable geographical barrier to gene flow between populations in Ireland and Britain; however, some immigration from the Isle of Man to Ireland was detected. The results are discussed in the context of the recent commercialization of bumblebees for the European horticultural industry.

Deer populations inhabiting urban areas in the south of Spain: habitat and conflicts - Jesús Duarte; Miguel A. Farfán; Julia E. Fa; J. Mario Vargas (European Journal of Wildlife Research, 2015)

Contribution of Coagulation–Flocculation Process for a More Sustainable Pig Slurry Management - R. A. Fragoso; E. A. Duarte; J. Paiva (Water, Air, & Soil Pollution, 2015)

Occurrence and analysis of endocrine-disrupting compounds in a water supply system - A. R. M Carvalho; V. V. Cardoso; A. Rodrigues; E. Ferreira; M. J. Benoliel; E. A. Duarte (Environmental Monitoring and Assessment, 2015)

Geochemistry, mineralogy, solid-phase fractionation and oral bioaccessibility of lead in urban soils of Lisbon - A. P. Reis; C. Patinha; J. Wragg; A. C. Dias; M. Cave; A. J. Sousa; C. Costa; A. Cachada; E. Ferreira da Silva; F. Rocha; A. Duarte (Environmental Geochemistry and Health, 2014)

Yield and water productivity of five chickpea varieties under supplemental irrigation in contrasting years - L. L. Silva; I. Duarte; E. Lourenço; N. Simões; M. M. Chaves (Irrigation Science, 2014)

Mercury accumulation and tissue-specific antioxidant efficiency in the wild European sea bass (Dicentrarchus labrax) with emphasis on seasonality - C. L. Mieiro; M. Dolbeth; T. A. Marques; A. C. Duarte; M. E. Pereira; M. Pacheco (Environmental Science and Pollution Research, 2014)

Response of a dung beetle assemblage along a reforestation gradient in Restinga forest - Malva I. M. Hernández; Pedro S. C. S. Barreto; Valderêz H. Costa; Antonio J. Creão-Duarte; Mario E. Favila (Journal of Insect Conservation, 2014)

Highly polymorphic microsatellite markers for the Mediterranean endemic fan mussel Pinna nobilis - M. GONZALEZ-WANGUEMERT; J. COSTA; L. BASSO; C. DUARTE; E. SERRÃO; I. HENDRIKS (Mediterranean Marine Science, 2014)
Pinna nobilis is an endemic bivalve of the Mediterranean Sea whose populations have decreased in the last decades due to human pressure; as consequence, it was declared a protected species in 1992. Despite its conservation status, few genetic studies using mitochondrial markers have been published. We report on the isolation and development of 10 microsatellite loci for the fan mussel, Pinna nobilis. All loci (2 di-nucleotide, 5 tri-nucleotide, 2 tetra-nucleotide and 1 penta-nucleotide) are characterized by high polymorphism levels in 76 individuals tested from two populations in Balearic Islands (Spain, Western Mediterranean Sea). Number of alleles ranged from 4 to 24 and expected heterozygosity ranged from 0.4269 to 0.9400. These microsatellites could be very useful to assess the genetic diversity and connectivity patterns of P. nobilis and to establish new conservation strategies.

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

Blowflies (Diptera, Calliphoridae) Associated with Pig Carcasses in a Caatinga Area, Northeastern Brazil - A C F Alves; W E Santos; R C A P Farias; A J Creão-Duarte (Neotropical Entomology, 2014)

Time flies when you are in a groove: using entrainment to mechanical resonance to teach a desired movement distorts the perception of the movement’s timing - Daniel K. Zondervan; Jaime E. Duarte; Justin B. Rowe; David J. Reinkensmeyer (Experimental Brain Research, 2014)

Cork stoppers as an effective sorbent for water treatment: the removal of mercury at environmentally relevant concentrations and conditions - Cláudia B. Lopes; Joana R. Oliveira; Luciana S. Rocha; Daniela S. Tavares; Carlos M. Silva; Susana P. Silva; Niels Hartog; Armando C. Duarte; E. Pereira (Environmental Science and Pollution Research, 2014)

Climate effects on amphibian distributions depend on phylogenetic resolution and the biogeographical history of taxa - L. D. S. Duarte; C. Both; V. J. Debastiani; M. B. Carlucci; L. O. Gonçalves; L. Cappelatti; G. D. S. Seger; V. A. G. Bastazini; F. T. Brum; E. V. Salengue; J. S. Bernardo‐Silva (Global Ecology and Biogeography, 2014)
Aim Disentangling the effects of climate and historical factors on biodiversity distribution remains a challenge for biogeographers. Here, we provide an analytical framework to discriminate the contributions of contemporary climate and the biogeographical history of taxa to the geographical distributions of phylogenetic lineages. Furthermore, we evaluate the constraint that the biogeographical history of clades exerts on the association between climate and clade distribution, i.e. the historical legacy of climatic effects. As a case study, we analysed the distributions of amphibian lineages across the A mericas. Location The A mericas. Methods We tallied the number of amphibian species per genus in each of 262 ecoregions. Each ecoregion was described by the composition of phylogenetic lineages using phylogenetic fuzzy weighting. The composition of amphibian genera and phylogenetic clades represented the distributions of shallow and deep phylogenetic nodes, respectively. We characterized each ecoregion by the biogeographical history of amphibian taxa and its current climate, whose influences on shallow and deep phylogenetic nodes were analysed using variation partitioning analysis. Results The association between climate and the distributions of deep phylogenetic nodes showed a strong historical legacy, although the distribution of amphibian genera was mostly associated with climate. Hyloidea were associated with a G ondwanan origin and higher annual mean temperatures, whereas other clades (e.g. C audata) were related to a L aurasian origin and higher temperature seasonality. Microhylidae were related to occurrence in the E arly J urassic in G ondwana and recent occurrence in the N eotropics. Main conclusions Biogeographical patterns can be thought of as the net outcome of evolutionary, historical and ecological processes. Although temperature is likely to affect the ecology of amphibians, the effects of climate on the distributions of deep phylogenetic nodes were strongly constrained by the biogeographical history of clades. Nevertheless, local, climatically driven processes are likely to influence the distributions of shallow phylogenetic nodes. The historical biogeography of clades might help to explain the interplay between evolutionary and environmental processes in determining assembly patterns found elsewhere.

Mapping Hotspots of Threatened Species Traded in Bushmeat Markets in the Cross–Sanaga Rivers Region - JULIA E. FA; MIGUEL ANGEL FARFÁN; ANA LUZ MARQUEZ; JESÚS DUARTE; JANET NACKONEY; AMY HALL; JEF DUPAIN; SARAH SEYMOUR; PAUL J. JOHNSON; DAVID W. MACDONALD; J. MARIO VARGAS (Conservation Biology, 2014)
Bushmeat markets exist in many countries in West and Central Africa, and data on species sold can be used to detect patterns of wildlife trade in a region. We surveyed 89 markets within the Cross–Sanaga rivers region, West Africa. In each market, we counted the number of carcasses of each taxon sold. During a 6‐month period (7594 market days), 44 mammal species were traded. Thirteen species were on the International Union for Conservation of Nature (IUCN) Red List or protected under national legislation, and at least 1 threatened species was traded in 88 of the 89 markets. We used these data to identify market groups that traded similar species assemblages. Using cluster analyses, we detected 8 market groups that were also geographically distinct. Market groups differed in the diversity of species, evenness of species, and dominant, prevalent, and characteristic species traded. We mapped the distribution of number of threatened species traded across the study region. Most threatened species were sold in markets nearest 2 national parks, Korup National Park in Cameroon and Cross River in Nigeria. To assess whether the threatened‐species trade hotspots coincided with the known ranges of these species, we mapped the overlap of all threatened species traded. Markets selling more threatened species overlapped with those regions that had higher numbers of these. Our study can provide wildlife managers in the region with better tools to discern zones within which to focus policing efforts and reduce threats to species that are threatened by the bushmeat trade. Mapeo de Sitios Críticos para Especies Amenazadas Comercializadas en Mercados de Vida Silvestre en la Región de los Ríos Cross‐Sanaga

ECONOMIC RISK ANALYSIS OF TOMATO IRRIGATION USING DESALINATED WATER BY REVERSE OSMOSIS - T. M. Soares; C.D.G.C. Almeida; J. A. Frizzone; E. F. F. Silva; S. N. Duarte (Irrigation and Drainage, 2013)
Groundwater desalination by reverse osmosis is an alternative being used more and more in Brazil, especially in the north‐east region, and aims to provide fresh water in isolated communities. Desalination to produce water for irrigation is a subject on which there has been minimal study. This research evaluated the economic feasibility of desalination for tomato ( Lycopersicon esculentum Mill) irrigation. By the Monte Carlo method, applied to the net present worth (NPW), a probabilistic analysis of risk was accomplished for tomato irrigation using 21 scenarios, comprising different irrigation waters (EC (electrical conductivity) 1, 2, 3, 4, 5 or 6 dS m ‐1 ), desalinated water and three yield levels (100, 70 and 40 Mg ha ‐1 ) obtained under non‐saline water conditions. For each scenario, 5000 values of NPW were simulated, and net present worth expectation, E (NPW), was estimated. Desalination for tomato irrigation is just justified for waters with salinity levels higher than its salinity threshold. Tomato irrigation with desalinated water presents economic feasibility dependent on the yield level which would be reached under non‐saline conditions. Even using water with 6 dS m ‐1 , there was economic feasibility above 75% in desalination for tomato irrigation at all the levels of the designed yield. Copyright © 2013 John Wiley & Sons, Ltd.

Mercury bioaccumulation and the population dynamics of Mesopodopsis slabberi (Crustacea: Mysidacea) along a mercury contamination gradient - M. D’Ambrosio; S. C. Marques; U. M. Azeiteiro; M. A. Pardal; E. Pereira; A. C. Duarte; P. G. Cardoso (Ecotoxicology, 2013)

Nitrate reductase is required for the transcriptional modulation and bactericidal activity of nitric oxide during the defense response of Arabidopsis thaliana against Pseudomonas syringae - Simone C. Vitor; Gustavo T. Duarte; Elzira E. Saviani; Michel G. A. Vincentz; Halley C. Oliveira; Ione Salgado (Planta, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Valuation of Unmodified Rice Husk Waste as an Eco-Friendly Sorbent to Remove Mercury: a Study Using Environmental Realistic Concentrations - Luciana S. Rocha; Cláudia B. Lopes; J. A. Borges; A. C. Duarte; E. Pereira (Water, Air, & Soil Pollution, 2013)

Calibration and validation of SALTMED model under dry and wet year conditions using chickpea field data from Southern Portugal - L. L. Silva; R. Ragab; I. Duarte; E. Lourenço; N. Simões; M. M. Chaves (Irrigation Science, 2013)

Species‐specific ontogenetic diet shifts among Neotropical Crenicichla : using stable isotopes and tissue stoichiometry - E. D. Burress; A. Duarte; W. S. Serra; M. M. Gangloff; L. Siefferman (Journal of Fish Biology, 2013)
Ontogenetic diet shifts were compared among five sympatric pike cichlids Crenicichla in a subtropical South American stream using stable C and N isotopes and tissue stoichiometry (C:N). Within species, stable N isotopes were positively related to body size while C:N showed negative relationships. Stable C isotopes, however, were not related to body size in any species. By modelling the switch to piscivory using gut content‐isotope‐body size relationships, diet shifts were shown to be species‐specific with regard to both rate and degree of piscivory. Compared to other piscivorous lineages, Crenicichla appear to be unusually small‐bodied (based on maximum body size). Because of their diversity, abundance and dynamic size‐structured functional roles, Crenicichla may exert broad and complex predation pressures on the aquatic community.

Impacts of ocean acidification on marine organisms: quantifying sensitivities and interaction with warming - Kristy J. Kroeker; Rebecca L. Kordas; Ryan Crim; Iris E. Hendriks; Laura Ramajo; Gerald S. Singh; Carlos M. Duarte; Jean‐Pierre Gattuso (Global Change Biology, 2013)
Ocean acidification represents a threat to marine species worldwide, and forecasting the ecological impacts of acidification is a high priority for science, management, and policy. As research on the topic expands at an exponential rate, a comprehensive understanding of the variability in organisms' responses and corresponding levels of certainty is necessary to forecast the ecological effects. Here, we perform the most comprehensive meta‐analysis to date by synthesizing the results of 228 studies examining biological responses to ocean acidification. The results reveal decreased survival, calcification, growth, development and abundance in response to acidification when the broad range of marine organisms is pooled together. However, the magnitude of these responses varies among taxonomic groups, suggesting there is some predictable trait‐based variation in sensitivity, despite the investigation of approximately 100 new species in recent research. The results also reveal an enhanced sensitivity of mollusk larvae, but suggest that an enhanced sensitivity of early life history stages is not universal across all taxonomic groups. In addition, the variability in species' responses is enhanced when they are exposed to acidification in multi‐species assemblages, suggesting that it is important to consider indirect effects and exercise caution when forecasting abundance patterns from single‐species laboratory experiments. Furthermore, the results suggest that other factors, such as nutritional status or source population, could cause substantial variation in organisms' responses. Last, the results highlight a trend towards enhanced sensitivity to acidification when taxa are concurrently exposed to elevated seawater temperature.

Contrasts in Livelihoods and Protein Intake between Commercial and Subsistence Bushmeat Hunters in Two Villages on Bioko Island, Equatorial Guinea - MARÍA GRANDE VEGA; BRUNO CARPINETTI; JESÚS DUARTE; JULIA E. FA (Conservation Biology, 2013)
Across West and Central Africa, wildlife provides a source of food and income. We investigated the relation between bushmeat hunting and household wealth and protein consumption in 2 rural communities in Bioko Island, Equatorial Guinea. One village was dedicated to commercial hunting, the other trapped game primarily for food. We tested whether commercial‐hunter households were nutritionally advantaged over subsistence‐hunter households due to their higher income from the bushmeat trade and greater access to wild‐animal protein. We conducted bushmeat‐offtake surveys in both villages (captures by hunters and carcasses arriving to each village). Mammals (including threatened primates: black colobus [ Colobus satanas ], Preussi's guenon [ Allochrocebus preussi ], and russet‐eared guenon [ Cercopithecus erythrotis ]), birds, and reptiles were hunted. The blue duiker ( Philantomba monticola ), giant pouched rat ( Cricetomys emini ), and brush‐tailed porcupine ( Atherurus africanus ) contributed almost all the animal biomass hunted, consumed, or sold in both villages. Monkeys and Ogilbyi's duikers ( Cephalophus ogilbyi ) were hunted only by commercial hunters. Commercial hunters generated a mean of US$2000/year from bushmeat sales. Households with commercial hunters were on average wealthier, generated more income, spent more money on nonessential goods, and bought more products they did not grow. By contrast, households with subsistence hunters spent less on market items, spent more on essential products, and grew more of their own food. Despite these differences, average consumption of vegetable protein and domestic meat and bushmeat protein did not differ between villages. Our results highlight the importance of understanding the socioeconomic and nutritional context of commercial and subsistence bushmeat hunting to correctly interpret ways of reducing their effects on threatened species and to enable the sustainable offtake of more productive taxa . Contrastes en el Sustento y la Ingesta de Proteínas entre Carne de Caza de Subsistencia y Comercial en Dos Aldeas en Isla Bioko, Guinea Ecuatorial

Glutathione and its dependent enzymes’ modulatory responses to toxic metals and metalloids in fish—a review - K. Srikanth; E. Pereira; A. C. Duarte; I. Ahmad (Environmental Science and Pollution Research, 2013)

Is Ocean Acidification an Open-Ocean Syndrome? Understanding Anthropogenic Impacts on Seawater pH - Carlos M. Duarte; Iris E. Hendriks; Tommy S. Moore; Ylva S. Olsen; Alexandra Steckbauer; Laura Ramajo; Jacob Carstensen; Julie A. Trotter; Malcolm McCulloch (Estuaries and Coasts, 2013)

Major inputs and mobility of potentially toxic elements contamination in urban areas - A. Cachada; A. C. Dias; P. Pato; C. Mieiro; T. Rocha-Santos; M. E. Pereira; E. Ferreira da Silva; A. C. Duarte (Environmental Monitoring and Assessment, 2013)

Derivation of soil to plant transfer functions for metals and metalloids: impact of contaminant’s availability - S. M. Rodrigues; E. Pereira; A. C. Duarte; P. F. A. M. Römkens (Plant and Soil, 2012)

Vitamin D receptor polymorphisms in hypertensive disorders of pregnancy - Vania B. Rezende; Valeria C. Sandrim; Ana C. Palei; Lorena Machado; Ricardo C. Cavalli; Geraldo Duarte; Jose E. Tanus-Santos (Molecular Biology Reports, 2012)

Net primary productivity, upwelling and coastal currents in the Gulf of Ulloa, Baja California, México - E. González-Rodríguez; A. Trasviña-Castro; G. Gaxiola-Castro; L. Zamudio; R. Cervantes-Duarte (Ocean Science, 2012)
The Gulf of Ulloa, a highly productive area off the western coast of the Baja California Peninsula, is examined for five successive years (2003–2007) by using satellite data and seasonal net primary productivity (NPP) estimates obtained from a vertical generalised production model. The results identify that northwestern winds blow parallel to the coast throughout the year. However, highest NPP occurs from March to June. During this period, an equatorward coastal current transports water from neighbouring upwelling areas to the northern Gulf of Ulloa and in combination with local upwelling, which injects nutrients into the euphotic zone, produce the observed increase in NPP. The opposite situation occurs in late summer when a warm poleward current of tropical characteristics arrives and inhibits the productivity in the whole region and generates the yearly lowest NPP levels. Our findings reveal the importance of lateral advection in the modulation of the primary productivity in this subtropical upwelling region.

Evaluation of Species-Specific Dissimilarities in Two Marine Fish Species: Mercury Accumulation as a Function of Metal Levels in Consumed Prey - C. L. Mieiro; J. P. Coelho; M. Pacheco; A. C. Duarte; M. E. Pereira (Archives of Environmental Contamination and Toxicology, 2012)

Removal of Arsenic from Aqueous Solutions by Sorption onto Sewage Sludge-Based Sorbent - Daniela S. Tavares; Cláudia B. Lopes; João P. Coelho; Marta E. Sánchez; Ana I. Garcia; Armando C. Duarte; Marta Otero; Eduarda Pereira (Water, Air, & Soil Pollution, 2012)

Genetic variability of banana with ornamental potential - Everton Hilo de Souza; Maria Angélica Pereira de Carvalho Costa; Fernanda Vidigal Duarte Souza; Davi Silva Costa Junior; Edson Perito Amorim; Sebastião de Oliveira e Silva; Janay Almeida dos Santos-Serejo (Euphytica, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

The field resistance of potato cultivars to foliar late blight and its relationship with foliage maturity type and skin type in Brazil - H. S. S. Duarte; L. Zambolim; E. S. G. Mizubuti; J. G. Pádua; J. I. Ribeiro Júnior; E. L. Carmo; A. F. Nogueira Júnior (Australasian Plant Pathology, 2012)

Tipping Elements in the Arctic Marine Ecosystem - Carlos M. Duarte; Susana Agustí; Paul Wassmann; Jesús M. Arrieta; Miquel Alcaraz; Alexandra Coello; Núria Marbà; Iris E. Hendriks; Johnna Holding; Iñigo García-Zarandona; Emma Kritzberg; Dolors Vaqué (Ambio, 2012)

Phylogenetics and predictive distribution modeling provide insights into the geographic divergence of Eriosyce subgen. Neoporteria (Cactaceae) - Pablo C. Guerrero; Mary T. K. Arroyo; Ramiro O. Bustamante; Milén Duarte; Thomas K. Hagemann; Helmut E. Walter (Plant Systematics and Evolution, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Seagrass Meadows Modify Drag Forces on the Shell of the Fan Mussel Pinna nobilis - Iris E. Hendriks; Miguel Cabanellas-Reboredo; Tjeerd J. Bouma; Salud Deudero; Carlos M. Duarte (Estuaries and Coasts, 2011)

The role of arctic zooplankton in biogeochemical cycles: respiration and excretion of ammonia and phosphate during summer - M. Alcaraz; R. Almeda; A. Calbet; E. Saiz; C. M. Duarte; S. Lasternas; S. Agustí; R. Santiago; J. Movilla; A. Alonso (Polar Biology, 2010)

Perinatal l-arginine and antioxidant supplements reduce adult blood pressure but not ameliorate the altered vascular function in spontaneously hypertensive rats - Diego B. de Queiroz; Fernanda E. Ramos-Alves; Raphaella L. Fernandes; Cíntia P. Zuzu; Glória P. Duarte; Fabiano E. Xavier (Journal of Physiology and Biochemistry, 2010)

Allelochemical Effects of Volatile Compounds and Organic Extracts from Muscodor yucatanensis, a Tropical Endophytic Fungus from Bursera simaruba - Martha L. Macías-Rubalcava; Blanca E. Hernández-Bautista; Fabiola Oropeza; Georgina Duarte; María C. González; Anthony E. Glenn; Richard T. Hanlin; Ana Luisa Anaya (Journal of Chemical Ecology, 2010)

Are Great Tits (Parus major) Inhabiting the Vicinity of a Pulp Mill Healthy? Impacts on Physiology and Breeding Performance - Ana Cláudia Norte; B. C. Sheldon; J. P. Sousa; P. C. Tavares; M. E. Pereira; A. C. Duarte; J. A. Ramos (Archives of Environmental Contamination and Toxicology, 2010)

Antioxidant system breakdown in brain of feral golden grey mullet (Liza aurata) as an effect of mercury exposure - C. L. Mieiro; I. Ahmad; M. E. Pereira; A. C. Duarte; M. Pacheco (Ecotoxicology, 2010)

Genetic similarity among genotypes of sugarcane estimated by SSR and coefficient of parentage - L. S. C. Duarte Filho; P. P. Silva; J. M. Santos; G. V. S. Barbosa; C. E. Ramalho-Neto; L. Soares; J. C. F. Andrade; C. Almeida (Sugar Tech, 2010)

Evolution of fluid geochemistry at the Turrialba volcano (Costa Rica) from 1998 to 2008 - O. Vaselli; Franco Tassi; E. Duarte; E. Fernandez; R. J. Poreda; A. Delgado Huertas (Bulletin of Volcanology, 2010)

Effects of seagrasses and algae of the Caulerpa family on hydrodynamics and particle-trapping rates - Iris E. Hendriks; Tjeerd J. Bouma; Edward P. Morris; Carlos M. Duarte (Marine Biology, 2010)

Genetic structure in the Mediterranean seagrass Posidonia oceanica : disentangling past vicariance events from contemporary patterns of gene flow - I. A. SERRA; A. M. INNOCENTI; G. DI MAIDA; S. CALVO; M. MIGLIACCIO; E. ZAMBIANCHI; C. PIZZIGALLI; S. ARNAUD-HAOND; C. M. DUARTE; E. A. SERRAO; G. PROCACCINI (Molecular Ecology, 2010)

Effects of sulfated polysaccharide and alcoholic extracts from green seaweed Ulva fasciata on anthracnose severity and growth of common bean (Phaseolus vulgaris L.) - R. Paulert; V. Talamini; J. E. F. Cassolato; M. E. R. Duarte; M. D. Noseda; A. Smania; M. J. Stadnik (Journal of Plant Diseases and Protection, 2009)

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment - M. E. Pereira; A. I. Lillebø; P. Pato; M. Válega; J. P. Coelho; C. B. Lopes; S. Rodrigues; A. Cachada; M. Otero; M. A. Pardal; A. C. Duarte (Environmental Monitoring and Assessment, 2009)

Fraction images derived from Terra Modis data for mapping burnt areas in Brazilian Amazonia - Y. E. Shimabukuro; V. Duarte; E. Arai; R. M. Freitas; A. Lima; D. M. Valeriano; I. F. Brown; M. L. R. Maldonado (International Journal of Remote Sensing, 2009)

Metabolic activity interferometer: description and calibration of an interferometric method to measure growth of mycobacteria - R. R. P. Machado; E. S. Lima Filho; D. F. Jardim; M. A. A. Ferreira; C. G. de Faria; R. S. Duarte; B. Lesche (European Biophysics Journal, 2008)

Otolith microstructure analysis with OTC validation confirms age overestimation in Atlantic thread herring Opisthonema oglinum from north‐eastern Brazil - R. Lessa; P. Duarte‐Neto; E. Morize; R. Maciel (Journal of Fish Biology, 2008)
The daily periodicity of micro‐increments in the otoliths of Atlantic thread herring Opisthonema oglinum was demonstrated from juveniles injected with oxytetracycline and reared for up to 62 days. Micro‐increments ranged from 26 to 358 in the overall sample. Von Bertalanffy growth function (VBGF) using micro‐increment counts were: L ∞ = 337 mm fork length ( L F ) ( s . e . = 31 mm); K = 1·2 ( s . e . = 0·2) and t 0 = 0·04 years ( s . e . = 0·01 years). The otolith‐based growth was corroborated using the L F frequency analysis. Observed lengths of increments were considered unsuitable for VBGF derivation, as no increase in size was obtained from them. Furthermore, the high percentage of unreadable otoliths suggests that increment analysis is unreliable for age estimation. Most growth occurs within the first year, differing from previous longevity estimates of 4–8 years. In contrast with published information, O. oglinum is a fast‐growing and short‐lived species.

IL6 (-174) and TNFA (-308) promoter polymorphisms are associated with systemic creatine kinase response to eccentric exercise - Chen Yamin; José Alberto Ramos Duarte; José Manuel Fernandes Oliveira; Offer Amir; Moran Sagiv; Nir Eynon; Michael Sagiv; Ruthie E. Amir (European Journal of Applied Physiology, 2008)

Evaluation of tests to assess the quality of mine-contaminated soils - P. Alvarenga; P. Palma; A. P. Gonçalves; R. M. Fernandes; A. de Varennes; G. Vallini; E. Duarte; A. C. Cunha-Queda (Environmental Geochemistry and Health, 2008)

Standardizing methods to address clonality in population studies - S. ARNAUD‐HAOND; C. M. DUARTE; F. ALBERTO; E. A. SERRÃO (Molecular Ecology, 2007)
Although clonal species are dominant in many habitats, from unicellular organisms to plants and animals, ecological and particularly evolutionary studies on clonal species have been strongly limited by the difficulty in assessing the number, size and longevity of genetic individuals within a population. The development of molecular markers has allowed progress in this area, and although allozymes remain of limited use due to their typically low level of polymorphism, more polymorphic markers have been discovered during the last decades, supplying powerful tools to overcome the problem of clonality assessment. However, population genetics studies on clonal organisms lack a standardized framework to assess clonality, and to adapt conventional data analyses to account for the potential bias due to the possible replication of the same individuals in the sampling. Moreover, existing studies used a variety of indices to describe clonal diversity and structure such that comparison among studies is difficult at best. We emphasize the need for standardizing studies on clonal organisms, and particularly on clonal plants, in order to clarify the way clonality is taken into account in sampling designs and data analysis, and to allow further comparison of results reported in distinct studies. In order to provide a first step towards a standardized framework to address clonality in population studies, we review, on the basis of a thorough revision of the literature on population structure of clonal plants and of a complementary revision on other clonal organisms, the indices and statistics used so far to estimate genotypic or clonal diversity and to describe clonal structure in plants. We examine their advantages and weaknesses as well as various conceptual issues associated with statistical analyses of population genetics data on clonal organisms. We do so by testing them on results from simulations, as well as on two empirical data sets of microsatellites of the seagrasses Posidonia oceanica and Cymodocea nodosa . Finally, we also propose a selection of new indices and methods to estimate clonal diversity and describe clonal structure in a way that should facilitate comparison between future studies on clonal plants, most of which may be of interest for clonal organisms in general.

Genetic structure of the diploid–polyploid fish Squalius alburnoides in southern Iberian basins Tejo and Guadiana, based on microsatellites - M. E. Crespo‐López; I. Pala; T. L. Duarte; T. E. Dowling; M. M. Coelho (Journal of Fish Biology, 2007)
Several studies have demonstrated the hybrid origin of Squalius alburnoides , a complex of diploid, triploid and tetraploid fish, with Squalius pyrenaicus as the maternal ancestor and an Anaecypris hispanica ‐like species as the paternal ancestor. The aim of this study was to assess patterns of genetic diversity and similarity between sympatric forms of the different ploidy levels of S. alburnoides and related parental species in the two largest basins that are part of its southern Iberian distribution, the Tejo and Guadiana, using microsatellites. High levels of genetic diversity were found in populations of S. alburnoides from both basins, reflecting the hybrid origin, the high diversity of forms in these river basins and the different modes of reproduction of the complex. Microsatellites indicated low values of genetic differentiation between the non‐hybrid all‐male form of S. alburnoides and A. hispanica , supporting the view that these forms share a common ancestor. In some instances, diploid and triploid hybrids from the same river basin were more closely related to each other than to their counterparts in the other basins, suggesting an ancient origin for the complex in these Iberian southern basins.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Community structure of the macroinfauna inhabiting tidal flats characterized by the presence of different species of burrowing bivalves in Southern Chile - E. Jaramillo; H. Contreras; C. Duarte (Hydrobiologia, 2007)

Spatial and temporal variation in the elemental and stable isotopic content of the seagrasses Posidonia oceanica and Cymodocea nodosa from the Illes Balears, Spain - J. W. Fourqurean; N. Marbà; C. M. Duarte; E. Diaz-Almela; S. Ruiz-Halpern (Marine Biology, 2007)

Genetic structure at range edge: low diversity and high inbreeding in Southeast Asian mangrove ( Avicennia marina ) populations - S. ARNAUD‐HAOND; S. TEIXEIRA; S. I. MASSA; C. BILLOT; P. SAENGER; G. COUPLAND; C. M. DUARTE; E. A. SERRÃO (Molecular Ecology, 2006)
Understanding the genetic composition and mating systems of edge populations provides important insights into the environmental and demographic factors shaping species’ distribution ranges. We analysed samples of the mangrove Avicennia marina from Vietnam, northern Philippines and Australia, with microsatellite markers. We compared genetic diversity and structure in edge (Southeast Asia, and Southern Australia) and core (North and Eastern Australia) populations, and also compared our results with previously published data from core and southern edge populations. Comparisons highlighted significantly reduced gene diversity and higher genetic structure in both margins compared to core populations, which can be attributed to very low effective population size, pollinator scarcity and high environmental pressure at distribution margins. The estimated level of inbreeding was significantly higher in northeastern populations compared to core and southern populations. This suggests that despite the high genetic load usually associated with inbreeding, inbreeding or even selfing may be advantageous in margin habitats due to the possible advantages of reproductive assurance, or local adaptation. The very high level of genetic structure and inbreeding show that populations of A. marina are functioning as independent evolutionary units more than as components of a metapopulation system connected by gene flow. The combinations of those characteristics make these peripheral populations likely to develop local adaptations and therefore to be of particular interest for conservation strategies as well as for adaptation to possible future environmental changes.

Phylogeography and Pleistocene demographic history of the endangered marsh deer (Blastocerus dichotomus) from the Río de la Plata Basin - Alejandro Márquez; J. E. Maldonado; S. González; M. D. Beccaceci; J. E. Garcia; J. M. B. Duarte (Conservation Genetics, 2006)

Determination of Organic Mercury in Biota, Plants and Contaminated Sediments Using a Thermal Atomic Absorption Spectrometry Technique - M. Válega; S. Abreu; P. Pato; L. Rocha; A. R. Gomes; M. E. Pereira; A. C. Duarte (Water, Air, & Soil Pollution, 2006)

Physiological synecology of tree species in relation to geographic distribution and ecophysiological parameters at the Atlantic forest periphery in Brazil: an overview - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; H. Rennenberg; U. Lüttge (Trees, 2006)

A comparative study of responses in plankton food web structure and function in contrasting European coastal waters exposed to experimental nutrient addition - Y. Olsen; S. Agustí; T. Andersen; C. M. Duarte; J. M. Gasol; I. Gismervik; A.-S. Heiskanen; E. Hoell; P. Kuuppo; R. Lignell; H. Reinertsen; U. Sommer; et al. (Limnology and Oceanography, 2006)
We quantify, compare, and generalize responses of experimental nutrient loadings (L N ) on planktonic community structure and function in coastal waters. Data were derived from three mesocosm experiments undertaken in Baltic (BAL), Mediterranean (MED), and Norwegian (NOR) coastal waters. A planktonic model with seven functional compartments and 30–32 different carbon flows fit to all three experiments was used as a framework for flow‐rate estimation and comparison. Flows were estimated on the basis of time series of measured biomass, some measured flows, and inverse modeling. Biomass and gross uptake rate of carbon of most groups increased linearly with increasing L N in the nutrient input range of 0–1 µmol N L −1 d −1 at all locations. The fate of the gross primary production (GPP) was similar in all systems. Autotrophic biomass varied by two orders of magnitude among locations, with the lowest biomass and response to nutrient addition in MED waters. The variation of GPP among sites was less than one order of magnitude. Mesozooplankton dominated by doliolids (Tunicata), but not those dominated by copepods, presumably exerted efficient control of the autotrophic biomass, thereby buffering responses of autotrophs to high nutrient input. Among the many factors that can modify the responses of autotrophs to nutrients, the time scale over which the enrichment is made and the precise mode of nutrient enrichment are important. We suggest a general concept that may contribute to a scientific basis for understanding and managing coastal eutrophication.

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE-Brazil II. Spatial and ontogenetic dynamics in Andira legalis, a deciduous legume tree - A. Geβler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; F. R. Scarano; H. L. T. Zaluar; H. Rennenberg (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE Brazil I. Performance of three different species of Clusia in an array of plant communities - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; H. L. T. Zaluar; U. Lüttge (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE—Brazil III. Three legume trees in a semi-deciduous dry forest - A. Geßler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; P. J. F. P. Rodrigues; F. R. Scarano; H. Rennenberg (Trees, 2005)

Physiological synecology of tree species in relation to geographic distribution and ecophysiological parameters at the Atlantic forest periphery in Brazil: an overview - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; H. Rennenberg; U. Lüttge (Trees, 2005)

Explosive activity and generation mechanisms of pyroclastic flows at Arenal volcano, Costa Rica between 1987 and 2001 - P. D. Cole; E. Fernandez; E. Duarte; A. M. Duncan (Bulletin of Volcanology, 2005)

In situ measurements of carbon and nitrogen distribution and composition, photochemical efficiency and stable isotope ratios in Araucaria angustifolia - A. C. Franco; H. M. Duarte; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; K. T. Ribeiro; F. R. Scarano; U. Lüttge (Trees, 2005)

Genetic Structure of Blastocerus dichotomus Populations in the Paraná River Basin (Brazil) Based on Protein Variability - E. J. F. de Oliveira; J. E. Garcia; E. P. B. Contel; J. M. B. Duarte (Biochemical Genetics, 2005)

Variation of Mercury Contamination in Chicks of Little Tern Sterna albifrons in Southwest Europe: Brood, Age, and Colony Related Effects - P. C. Tavares; L. R. Monteiro; R. J. Lopes; M. E. Pereira; A. C. Duarte; R. W. Furness (Bulletin of Environmental Contamination and Toxicology, 2005)

Competitive interactions in macroinfaunal animals of exposed sandy beaches - Jenifer E. Dugan; Eduardo Jaramillo; David M. Hubbard; Heraldo Contreras; Cristian Duarte (Oecologia, 2004)

Aflatoxin Binders II: Reduction of aflatoxin M1 in milk by sequestering agents of cows consuming aflatoxin in feed - Duarte E. Diaz; Winston M. Hagler; John T. Blackwelder; Julie A. Eve; Brinton A. Hopkins; Kevin L. Anderson; Frank T. Jones; Lon W. Whitlow (Mycopathologia, 2004)

Biotechnological applications of peroxidases - Carlos Regalado; Blanca E. García-Almendárez; Miguel A. Duarte-Vázquez (Phytochemistry Reviews, 2004)

Aflatoxin Binders I: In vitro binding assay for aflatoxin B1 by several potential sequestering agents - Duarte E. Diaz; Winston M. Hagler; Brinton A. Hopkins; Lon W. Whitlow (Mycopathologia, 2003)

The Response of Experimental Rocky Shore Communities to Nutrient Additions - Tor L. Bokn; Carlos M. Duarte; Morten F. Pedersen; Nuria Marba; Frithjof E. Moy; Cristina Barrn; Birger Bjerkeng; Jens Borum; Hartvig Christie; Silke Engelbert; Frank L. Fotel; Espen E. Hoell; et al. (Ecosystems, 2003)

Cerebral Toxoplasmosis After Autologous Peripheral Blood Stem Cell Transplantation - M. Lpez-Duarte; A. Insunza; E. Conde; A. Iriondo; F. Mazorra; A. Zubizarreta (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Factorial design and response surface optimization of crude violacein for Chromobacterium violaceum production - Armando S. Mendes; João E. de Carvalho; Marta C.T. Duarte; Nelson Durán; Roy E. Bruns (Biotechnology Letters, 2001)

Storage and export of mercury from a contaminated bay (Ria de Aveiro, Portugal) - E. Ramalhosa; P. Monterroso; S. Abreu; E. Pereira; C. Vale; A. Duarte (Wetlands Ecology and Management, 2001)

Polysaccharides from the red seaweed Bostrychia montagnei: chemical characterization - Miguel D. Noseda; Siumara Tulio; Maria E. R. Duarte (Journal of Applied Phycology, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Conservation genetics of the endangered Pampas deer ( Ozotoceros bezoarticus ) - S. GONZÁLEZ; J. E. MALDONADO; J. A. LEONARD; C. VILÀ; J. M. BARBANTI DUARTE; M. MERINO; N. BRUM‐ZORRILLA; R. K. WAYNE (Molecular Ecology, 1998)
The Pampas deer ( Ozotoceros bezoarticus L. 1758) is the most endangered neotropical cervid, and in the past occupied a wide range of open habitats including grassland, pampas, savanna, and cerrado (Brazil) from 5° to 41° S. To better understand the effect of habitat fragmentation on gene flow and genetic variation, and to uncover genetic units for conservation, we examined DNA sequences from the mitochondrial control region of 54 individuals from six localities distributed throughout the present geographical range of the Pampas deer. Our results suggest that the control region of the Pampas deer is one of the most polymorphic of any mammal. This remarkably high variability probably reflects large historic population sizes of millions of individuals in contrast to numbers of fewer than 80 000 today. Gene flow between populations is generally close to one migrant per generation and, with the exception of two populations from Argentina, all populations are significantly differentiated. The degree of gene flow was correlated with geographical distance between populations, a result consistent with limited dispersal being the primary determinant of genetic differentiation between populations. The molecular genetic results provide a mandate for habitat restoration and reintroduction of Pampas deer so that levels of genetic variation can be preserved and historic patterns of abundance can be reconstructed. However, the source of individuals for reintroduction generally should be from populations geographically closest to those now in danger of extinction.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Seasonal variability in mercury inputs into the Ria de Aveiro, Portugal - M. E. Pereira; A. C. Duarte; G. E. Millward (Aquatic Ecology, 1995)